1,25(OH)₂D₃ mitigates bronchopulmonary dysplasia via modulation of the TXNIP–NLRP3–GSDMD signaling pathway - Dongzhui Chen; Shuqiang Lin; Li Yang; Xiaojie He; Heng Cai; Qiuyue Zhang (Molecular Biology Reports, 2026)

Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Targeting EFEMP1 enhances chondrogenesis and inhibits hypertrophic differentiation in a spontaneous osteoarthritis mouse model - Yuhan Chang; Pei-Heng Jiang; Yung-Heng Hsu; Yu-Chih Lin; Chih-Chien Hu; Yi-Zhen Li; Steve Wen-Neng Ueng; Mei-Feng Chen (Journal of Molecular Medicine, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Enhancing herbaceous biomass combustion in an industrial-scale CFB boiler using iron-based oxygen carriers as bed material - Guang Sun; Lin Li; Chong Liu; Tianxin Li; Heng Liu; Lunbo Duan (Fuel, 2026)

Fold-crease induced paper wicking enhancement enabling rapid and high-yield plasma separation - Xianchang Wu; Tonghuan Zhan; Fuzhou Niu; Yange Huang; Heng Wang; Lin Hu; Bing Xu (Analytica Chimica Acta, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

MXene-enabled interfacial electronic modulation steers high-valent metal-oxo generation toward boosting water purification - Yong-Sheng Tan; Heng-Heng Guo; Peng-Peng Duan; Wei-Kang Wang; Yi-Lin Lu; Dong-Hua Xie; Qi-Nian Wang; Xing Zhang (Chemical Engineering Journal, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Molecular-level interaction mechanisms of humic acid and residual aluminum species in gypsum scaling during nanofiltration - Jinjin Jia; Xinlei Zhang; Dachao Lin; Jiaxuan Yang; Longfeng Hu; Weijia Gong; Guibai Li; Heng Liang (Water Research, 2026)

Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Halorubrum marinum sp. nov., Halorubrum rarum sp. nov., Halorubrum wangae sp. nov., Halorubrum shenae sp. nov., and Halorubrum zhoui sp. nov., halophilic archaea from coastal tidal flats, a saline lake, and a marine solar saltern - Qing-Di Li; Yang-Yang Wang; Chidiebele Nwankwo; Yao Hu; Xin-Yue Dong; Jing Hou; Xiang-Dong Chen; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

See and destroy bacterial spores: Visual detection and in situ inactivation using a terbium-porphyrin nanoplatform - Shan Sun; Ke Cheng; Jiayi Feng; Hongbo Juan; Kefeng Zhou; Mingyan Zhao; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Space-confined composition-gradient perovskite for computational microspectrometer - Zhenhua Zhang; Hanyu Cui; Chenyan Zhuang; Xiaoxuan Wang; Heng Guo; Baohao Lin; Wanyu Wang; Wendong Lu; Zengliang Shi; Chunxiang Xu (Chemical Engineering Journal, 2026)

A novel κ-carrageenase from Vibrio sp. C7 produces red algal–derived oligosaccharides that promote plant growth - Qianyu Lin; Haihui Tan; Peiyu Xu; Alejandra Moenne; Wenxia Wang; Tang Li; Heng Yin (Algal Research, 2026)

Correction: The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

EID1 blockade potentiates immunosurveillance against cancer metastasis via FPR1-mediated DC-NK crosstalk - Ziqi Jin; Xiao Zhang; Huijuan Zhang; Siying Qin; Siqi Zhang; Shuqing Zhang; Lin Xia; Peipei Li; Wen Xu; Peng Liu; Liwei Zhao; Ruidong Xue; et al. (Science China Life Sciences, 2026)

Halolitoreus marinus gen. Nov., sp. nov. and Halolitoreus rarus sp. nov., halophilic archaea isolated from diverse coastal tidal flats, and proposal of the novel family Halolitoreaceae fam. Nov. in the order Halobacteriales within the class Halobacteria - Jing Hou; Guo-Liang Xu; Shun Tan; Ya-Ling Mao; Yu-Jie Xin; Mu Cheng; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Retraction notice to “A systematic review of antibiotics and antibiotic resistance genes (ARGs) in mariculture wastewater: Antibiotics removal by microalgal-bacterial symbiotic system (MBSS), ARGs characterization on the metagenomic” [Sci. Total Environ. 930 (2024) 172601] - Weijia Gong; Lin Guo; Chenxin Huang; Binghan Xie; Mengmeng Jiang; Yuzhou Zhao; Haotian Zhang; YuXuan Wu; Heng Liang (Science of The Total Environment, 2026)

Maternal PAN2 selectively maintains mRNA Poly(A) tail homeostasis to regulate RNA degradation during oocyte-to-early embryo transition in mice - Xuan Wu; Hua Zhang; Yu-Ke Wu; Zhuo-Yue Niu; Jing-Wen Liu; Lu Chen; Jia-Jia Cao; Yu-Lin Chen; Shu-Yan Ji; Fa-Long Lu; Heng-Yu Fan (Science Bulletin, 2026)

Regional exploitation signals inferred from a data-limited per-recruit assessment of Trichiurus japonicus in Taiwanese waters - Chih-Yu Lin; Yu-Heng Lu; Wen-Qi Xu; Sheng-Ping Wang; Toshihide Kitakado (Regional Studies in Marine Science, 2026)

FBG-based dynamic characterization of a scaled offshore wind turbine foundation model under impact and recorded seismic excitations - Jui-Chi Lin; Yi-Lun Liao; Bor-Yann Chen; I-Hsin Chiu; Wan-Yu Xu; You-Chen Liao; Yi-Heng Yang; Yu-Hsi Huang (Ocean Engineering, 2026)

Critical Role of Mid-Tropospheric Southwesterly Steering in a Failed Extreme Rainfall Simulation over Northeastern Qinghai–Xizang Plateau - Wei Si; Duming Gao; Xingwen Jiang; Peng Fan; Qing Zheng; Yong Feng; Zhiwei Heng; Dan Lin (Journal of Meteorological Research, 2026)

Reprogramming senescent granulosa cells for germ-cell generation - Dai Heng; Kairang Jin; Guoxing Yin; Chenglei Tian; Xiaoyan Sheng; Jiangtao Lu; Yiwei Wu; Xiaoying Ye; Panpan Shi; Huiyu Li; Chang Liu; Lin Liu; et al. (Science China Life Sciences, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

The dynamic evolution of circulating tumor cells during glecirasib treatment predicts survival and resistance in gastrointestinal tumors with KRASG12C mutation - Lei Jiang; Yiming Luo; Huan Liang; Xujiao Feng; Yan Huang; Yanyan Li; Zhenghang Wang; Ting Xu; Heng Zou; Zhi Li; Lin Shen; Yang Chen; et al. (Human Cell, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Sulfur-autotrophic treatment of Sb(V)-contaminated water across concentration levels: Toward effective antimony pollution control - Yahui Shi; Zhixiang Zhang; Heyu Wan; Lin Ma; Heng Chen; Ying Li; Jiahui Dai; Dongjin Wan (Process Safety and Environmental Protection, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Piezo-photocatalysis with BaTiO3 nanorod arrays–Ag nanoparticle composites for the photodegradation of rhodamine B - Yen-Lun Chiu; Thi Nghi Nhan Nguyen; Hsin-Yu Chi; Heng-Jun Lin; Kao-Shuo Chang (Journal of Environmental Chemical Engineering, 2026)

Enhanced antifriction and antiwear performances of steel achieved by porous boron nitride/grease composite triggered self-adaptive confined lubrication - Heng He; Fengli Zhou; He Huang; Songyan Cong; Beiyi Zhang; Weiben Chen; Yibing Lin; Li Qiang; Yuanlie Yu (Journal of Environmental Chemical Engineering, 2026)

Experimental and theoretical study on the ultimate bearing capacity of U-shaped steel-concrete composite cap beams - Heng Liu; Lin Xiao; Xing Wei; Xiang Li; Jian Ren; Huijun Wang (Engineering Structures, 2026)

Dynamic electronic and spin-state modulations of ternary single-atom catalysts for ultrahigh power density and ultra-stable rechargeable zinc-air batteries - Yu-Chieh Ting; Shao-I Chang; Kai-An Lee; Chiung-Wen Chang; Tzu-Hsiang Lin; Chih-Heng Lee; Hsin-Yi Tiffany Chen; Shih-Yuan Lu (Chemical Engineering Journal, 2026)

Unifying the Middle Jurassic major source rock system of the Qiangtang Basin: New chronological constraints from in situ calcite U-Pb dating - Shuqing Miao; Licheng Wang; Heng Peng; Yalin Li; Yahui Yue; Lin Ding (Science China Earth Sciences, 2026)

Two Novel Peniphenone Derivatives with Distinct Stereoconfigurations from Ascidian-Derived Fungus Diaporthe sp. SYSU-MS4722 and Their Anti-Fibrotic Activities - Shuya Ren; Yanhong Han; Yan Yan; Yuran Zhou; Siwen Yuan; Junjie Chen; Heng Guo; Zhenjian Lin; Qifeng Lin; Senhua Chen; Lan Liu; Yongkang Qiao; et al. (Journal of Ocean University of China, 2026)

Five novel Haloarchaeobius species from coastal tidal flats and saline-alkali soil in China using integrated culture-dependent and culture-independent approaches - Guo-Liang Xu; Shun Tan; Yao Hu; Mu Cheng; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Duration of high temperature-pressure conditions in impact-induced plumes on the Moon - Xiaoying Liu; Chi Zhang; Zongyu Yue; Lixin Gu; Jing Li; Heng-Ci Tian; Sen Hu; Yangting Lin (Icarus, 2026)

Formaldehyde activates the RUNX1–ISX axis to promote leukemic reprogramming, a pathway associated with poor prognosis in pediatric B-ALL - Pei-Chin Lin; Li-Ting Wang; Li-Heng Ye; Pin-Ying Tseng; Pei-Hsien Huang; Wan-Yi Hsu; Yu-Mei Liao; Shyh-Shin Chiou; Shih-Hsien Hsu (Environmental Pollution, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Comparative Online–offline measurement of airborne toxic VOCs for health risk and source identification in an environmental justice community - Hsin-Cheng Hsieh; Yuan-Chang Su; Sheng-Po Chen; Chen-Hsuan Chu; Mei-Hui Tseng; Kuan-Chun Lee; Po-Sheng Tseng; Pei-Hsuan Hsu; Chih-Chung Chang; Chieh-Heng Wang; Jia-Lin Wang (Atmospheric Environment, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

Plasma-assisted chemical looping reforming of benzene on Ce-NiMn2O4 oxygen carrier: Promoting effect and competitive mechanism of oxygen species - Aiqing Shao; Chun Wang; Linying Zhang; Yan Yang; Heng Chen; Yan Lin; Junguang Meng; Zhen Huang (Journal of Environmental Chemical Engineering, 2026)

Sources, sinks, and isotopic fractionation of antimony in a karst catchment: constraints on multi-media migration and biogeochemical cycling - Yu Lin; Guangyi Sun; Xinyu Li; Yunjie Wu; Yu Cheng; Heng Yao; Xinbin Feng (Geochimica et Cosmochimica Acta, 2026)

Thiourea-based networks with nanocarbon fillers for antistatic, self-healing, and plasma-resistant elastomers - Tse-Yu Lo; Shu-Fan Li; Chia-Wei Chang; Huan-Wei Lin; Heng-Hsuan Su; Kuan-Hung Liu; Po-Chia Huang; Jiun-Tai Chen (Chemical Engineering Journal, 2026)

A biomimetic molecular ‘tailor’ hydrogen bonds and ‘guide’ crystal planes to achieve dendritic-free zinc anodes - Haoran Lang; Chunyuan Xiong; Yufan Chen; Qiaoji Zheng; Yu Huo; Heng Zhang; Haoqi Yang; Dunmin Lin (Chemical Engineering Journal, 2026)

Decline in dust storm activity over northern China during 1961–2020: an examination of likely causes - Gangfeng Zhang; Yiwen Wang; Cesar Azorin-Molina; Lorenzo Minola; Kaiqiang Deng; Yaoyao Ma; Ziqi Lin; Heng Ma; Peijun Shi (Climatic Change, 2026)

Halovenus anhuiensis sp. nov. and Natronomonas salinimetallica sp. nov., two extremely halophilic archaeon isolated from a salt mine - Ya-Ling Mao; Aodi Zhang; Tao Hong; Yue Ding; Jingfang Liu; Jing Hou; Heng-Lin Cui; Shaoxing Chen (Extremophiles, 2026)

A novel method of estimating phytoplankton absorption coefficient for inland waters based on OLCI using Sun-induced chlorophyll-a fluorescence - Wenyu Liu; Yiling Zheng; Jie Lin; Yunmei Li; Honglei Guo; Huaiqing Liu; Yuxin Zhu; Fangfang Chen; Heng Lü; Song Miao (Journal of Oceanology and Limnology, 2026)

Haladaptatus marinus sp. nov., Haladaptatus rarus sp. nov., Haladaptatus ordinarius sp. nov., and Halomicrococcus pelagicus sp. nov., halophilic archaea from diverse coastal tidal flats - Xin-Ru Zhang; Jing Hou; Zhen Rong; Yue-Hong Wu; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Space weathering on the lunar nearside and farside revealed by iron and potassium isotopes - Heng-Ci Tian; Wei Yang; Xinmiao Zhao; Jun Du; Liyu Shan; Wen-Jun Li; Jing Wang; Xuhang Zhang; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Geochimica et Cosmochimica Acta, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

Chiral CD@Ag2O nanoparticle-mediated highly efficient antibacterial activity based on synergistic multi-pathway interactions - Xiang Li; Qi Ding; Si Li; Junru Li; Heng Zhang; Shan Sun; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2026)

Dual-track regulation of lattice respiration and interface stability: Zn2+ doping and electrolyte engineering towards strain-tolerant vanadium oxide cathodes - Xiangyue Liao; Yangjie Li; Jianding Li; Xiaoying Li; Min Xie; Jingxin Zhao; Heng Zhang; Bingang Xu; Dunmin Lin (Chemical Engineering Journal, 2026)

Ecotypic differentiation in motility and photoadaptation strategies between epibenthic and benthic Prorocentrum Lima complex - Jie Lin; Hua Zhang; Yiyi Cai; Songhui Lu; Heng Chen (Marine Biology, 2026)

Rapid microfluidic sample preparation for mass spectrometric analysis of wild-type and mutant BRAF protein - Yen-Heng Lin; Heng-Yun Chang; Chia-Chun Wu; Yung-Chin Hsiao; Ying-Hao Wen; Jau-Song Yu (Analytica Chimica Acta, 2026)

Marine heatwaves drive phytoplankton community shifts and chlorophyll a decline in the Bay of Bengal - Zhihao Yang; Pei Jiang; Yang Liu; Lin Deng; Zhimin Bai; Tuwang Li; Yuchen Liang; Zhongbing Chang; Heng Liu; Jun Zhao (Acta Oceanologica Sinica, 2026)

Whole-genome sequencing reveals the genetic diversity of Aeromonas from freshwater fish and the presence of novel genomic islands carrying clinically important antimicrobial resistance genes - Xiao-Qin Wang; Ke Wu; Run-Min Kang; Heng Lin; Lu-Ya Liu; Ting Xian; Yi-Zhi Tang; Xin Yang; An-Yun Zhang; Hong-Ning Wang; Chang-Wei Lei (Aquaculture, 2026)

Fluidized-bed crystallization of Li3PO4 from dilute lithium solutions at ambient temperature: Mechanistic insights and process implications - Heng-Sheng Chen; Jui-Yen Lin (Journal of Water Process Engineering, 2026)

Analysis of cadmium sources in surface soil in typical karst regions: Anthropogenic input contribution and atmospheric transport impact - Zhe Liu; Guangyi Sun; Xian Wu; Weihai Yu; Heng Yao; Yu Lin; Chunlin Fu; Jinling Liu; Xinbin Feng (Journal of Hazardous Materials, 2026)

Advancements in environmental microplastic removal and upcycling techniques - Tianyu Lin; Penggang Li; Huaping Jia; Heng Jiang; Fengjia Xie; Yanting Liu; James Kar-Hei Fang; Changchao Li; Xuming Zhang (Journal of Environmental Chemical Engineering, 2026)

Tectonic insights into the extensive Middle-Late Triassic terrestrial organic carbon burial in the North China Craton - Heng Peng; Lin Ding; Chiyang Liu; Massimiliano Zattin; Yahui Yue; Junfeng Zhao; Fulong Cai; Chao Wang; Hong Zhang; Pei Guo; Yun Jiang; Xiaoqin Jiao; et al. (Global and Planetary Change, 2026)

Mechanistic analysis of root morphology on shear behavior in root-soil composites using discrete element method (DEM) - Xiang-Hua Song; Yong Tan; Ping Hu; Pan-Pan Cheng; Heng-Lin Xiao (CATENA, 2026)

Correction: Research on the mise-à-la-masse method based on multi-frequency pseudo-random signals: a case study in the Baiquan Spring region, Jinan, China - Yang Yang; Zhi-de Li; Heng Zhang; Lin Wang; Jia-feng Mi (Hydrogeology Journal, 2026)

Experimental Study on Suppression and Mechanism of Sloshing Impact Pressure by Vertical Slat Screens Under Broadband Horizontal and Vertical Excitation - Liting Yu; Xiaoqian Luo; Jingcheng Lin; Jie Fan; Heng Jin (Journal of Marine Science and Engineering, 2026)
Sloshing-induced impact pressure is a key damage factor for marine liquid tanks. While research aimed at overcoming screen failure in sloshing suppression under high-frequency excitation has focused on wave height, the dataset of impact pressure remains lacking. Moreover, the pattern of pressure suppression under broadband excitation remains unclear. The primary contribution of this work is the first experimental dataset of impact pressure with vertical slat screens under broadband horizontal and vertical excitation. Second, it reveals pressure suppression patterns by screens across varying excitation frequencies and screen numbers. The results demonstrate that vertical slat screens can effectively suppress pressure. First, screen position matters more than number, proving that suppression is dominated by modal disturbance. Second, wave-height suppression does not reliably represent pressure suppression. Pressure suppression is systematically weaker. An exception occurs under vertical excitation, where pressure suppression can be stronger even when wave-height suppression fails. The results highlight the suppression mechanism dominated by modal disturbance and the instability inherent to parametric sloshing. Wave height, reflecting global potential energy, is effectively suppressed by modal disturbance. Pressure, originating from local kinetic energy, can be effectively suppressed by both modal disturbance and vortex dissipation.

Carbon quantum dot-induced bio-hybrid of Shewanella oneidensis MR-1 for enhanced extracellular hexavalent chromium reduction - Wenkang Zhang; Ke Shen; Fangjing Lin; Rongmei Tan; Heng Ding; Xiaojie Hu; Yanzheng Gao; Hefei Wang (Water Research, 2026)

Natronorubrum marinum sp. nov., Natronorubrum amylolyticum sp. nov., Natronorubrum halobium sp. nov., and Natronorubrum salinum sp. nov., halophilic archaea from a coastal saline-alkali land and two saline lakes - Ya-Ling Mao; Yao Hu; Zhang-Ping Wu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Physiological and molecular mechanisms underlying the deterioration of external quality in postharvest fresh lotus seed - Lin Chen; Heyun Song; Gangqiang Dong; Jia Xin; Mei Yang; Yanyan Su; Heng Sun (Postharvest Biology and Technology, 2026)

Cadmium accumulation and isotope fractionation in soil–oilseed rape (Brassica napus L.) system in a typical Karst region - Weihai Yu; Guangyi Sun; Heng Yao; Xian Wu; Zhe Liu; Yu Lin; Yu Cheng; Jiang Li; Hua Zhang; Xinbin Feng (Journal of Hazardous Materials, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Synthesis and leaching evaluation of entropy-stabilized zirconolite Ca(Zr,Hf,Sn)xTi3-xO7 (x = 0.8–2.2) - Qu Ai; Shi-Kuan Sun; Yu Tian; Wei-Dong Xiao; Yi Zhao; Sheng-Heng Tan; Wei-Ming Guo; Hua-Tay Lin (Chemical Engineering Journal, 2026)

Comparative study on organic composts in blueberry: insights into soil physicochemical properties and heavy metal control - Hao Tang; Ying Dai; Lijuan Tang; Juan Guo; Ke Wen; Fangke Yuan; Lin Li; Yuan Jin; Jinlu Li; Min Xiao; Heng Xu (Environmental Geochemistry and Health, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Tailoring the asymmetric structure of Cu-Co bimetallic catalysts to promote peroxydisulfate activation for pollutant degradation - Li-Ming Sun; Qin-Chen Li; Yong-Sheng Tan; Qi-Nian Wang; Yi-Lin Lu; Yi-Jun Zhang; Dong-Hua Xie; Heng-Heng Guo; Xing Zhang (Journal of Environmental Chemical Engineering, 2025)

A new insight of size-dependent plastics particles kinetics with regarding of metabolomics effects in liver and kidney - Hongying Gao; Jing Li; Zehua Xu; Yiyang Duan; Bowen Su; Mengting Li; Banyun Zheng; Miaomiao Ren; Hao Chang; Heng Wang; Yi Lin; Heqing Shen (Environmental Pollution, 2025)

Unveiling the role of Zn−N1S3 sites in atomic-precision ZnIn2S4/g-C3N4 heterostructure for highly efficient CO2-to-CO conversion - Hossam A.E. Omr; Raghunath Putikam; Mahmoud Kamal Hussien; Amr Sabbah; Tsai-Yu Lin; Kuei-Hsien Chen; Li-Chyong Chen; Heng-Liang Wu; Shien-Ping Feng; Ming-Chang Lin; Hyeonseok Lee (Chemical Engineering Journal, 2025)

Genetic mapping of novel QTL for seed protein stability in food-grade soybean (Glycine max) - Andrew A. Mitchell; Feng Lin; Heng Ye; Tri Vuong; Zixiang Wen; Biructawit Tessema; Randall Laurenz; Raju Thada Magar; Henry T. Nguyen; Dechun Wang (Theoretical and Applied Genetics, 2025)
Key message Two novel quantitative trait loci associated with soybean protein content stability were identified on chromosomes 10 and 18. Haplotype analysis showed these to significantly improve stability without protein content penalty. Abstract Soybean seed protein content is a complex physiological trait under polygenic control and significant genotype by environment interaction. Protein content is largely influenced by ambient atmospheric temperature at pod-filling, with increased temperatures enhancing seed protein accumulation. The identification of genomic regions associated with protein content stability will facilitate an increased understanding of seed development physiology and assist in the development of more broadly adapted food-grade soybean cultivars. In this work, 210 recombinant inbred lines were derived from the intraspecific cross of the high protein accession BARC - 6 (PI 555396), and the low protein MSU breeding accession E14077 for the investigation of quantitative trait loci associated with protein content and protein content stability across multiple years and test locations. Indices for static protein content stability were used to estimate genome by environment interactions across Northern and Southern soybean production regions. Composite interval mapping returned one stable major effect QTL associated with protein content on chromosome 20 explaining approximately 20.7% of phenotypic variation. Two novel QTLs associated with absolute protein stability were detected on chromosomes 10 and 18, explaining approximately 8.6% and 7.6% of phenotypic variation, respectively. SNP-based haplotype analysis showed simultaneous favorable effects on protein content and stability when desirable alleles for these QTL were pyramided. These results will serve as a valuable tool for the molecular breeding of food-grade soybean cultivars harboring elevated protein content coupled with improved stability across varied environments, thus addressing a key challenge in meeting the global rise in soybean protein demand for both livestock feed and human consumption.

A novel assessment method for stope stability in horizontal and gently inclined thin ore veins mining - Kunmeng Li; Xiaopeng Yang; Yueyue Ding; Yuanhui Li; Heng Li; Conglin Yuan; Lin Chen (Bulletin of Engineering Geology and the Environment, 2025)

Reduction of antibiotics and antibiotic resistance genes in simulated-sunlight-supported counter-diffusion bacteria-Algae biofilms: Interface properties and functional gene responses - Han Zhang; Jiao Yin; Haotian Jiang; Weichen Zeng; Yufei Cheng; Jiaxuan Yang; Dachao Lin; Langming Bai; Heng Liang (Water Research, 2025)

Biomineralization-driven simultaneous carbon/phosphorus recovery and membrane fouling control in anaerobic membrane bioreactor for swine wastewater treatment - Qianyi Liu; Hongyu Xie; Yin Xu; Ziang Zhou; Yuqi Chen; Lan Lin; Rasheed Adeleke; Heng Li; Yuanpeng Wang; Shaohua Chen; Yanlong Zhang (Water Research, 2025)

Evaluating impacts of hydrology and pollution loadings on low dissolved oxygen in an urbanized tidal river network using modeling and monitoring - Heng Zhang; Jiahuan Liu; Tong Li; Siyu Zhang; Zhongyuan Lin; Zhengbo Jia; Wenping Gong; Guang Zhang (Journal of Hydrology, 2025)

Heat exposure and adverse birth outcomes: Modification by residential greenness in a 14-year prospective cohort study in Taiwan - Ming-Lun Zou; Shih-Chun Candice Lung; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Yi-Yong Chen; Hsing-Jasmine Chao; Shih-Peng Mao; Pilyoung Kim; Wen-Yi Lin; Yi-Hua Chen (Environmental Research, 2025)

Biofilm management via loach predation: An eco-friendly approach to enhance membrane performance in wastewater treatment - Weijia Gong; Xianwu Liu; Yuzhou Zhao; Mengmeng Jiang; Lin Guo; Le Tong; Jinyan Lu; Jiaxuan Yang; Heng Liang; Xiaobin Tang (Chemical Engineering Journal, 2025)

Topography-engineered cobalt-based microparticles for biofilm-eradicating medical device disinfection: Overcoming antibacterial resistance through mechano-bactericidal action - Ke Cheng; Shan Sun; Wenhao Zheng; Heng Zhang; Henggang Wang; Shang Gao; Si Li; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Chirality-enhanced catalytic selectivity of vanadium oxide (V2O4/5) nanoparticles for higher detection sensitivity - Junru Li; Si Li; Shuhan He; Heng Zhang; Hengwei Lin; Peng Wang (Chemical Engineering Journal, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Biomimetic assembly of organic ferroelectrics induced tailorable domain reconfiguration for high-performance self-powered neuromorphic system - Heng Yao; Huang Lin; Zhaoyue Xia; Jing Wang; Yadong Jia; Xuexin Li; Daiwen Tao; Hui Yang; Qilong Zhang (Chemical Engineering Journal, 2025)

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Biofilm response in potential difference-enhanced membrane-aerated biofilm systems for accelerated antibiotic removal and ARG mitigation - Han Zhang; Haotian Jiang; Jiao Yin; Tianyi Wang; Weichen Zeng; Dachao Lin; Boyan Xu; Langming Bai; Heng Liang; How Yong Ng (Water Research, 2025)

An increase in wind erosion dominated by wind speed changes over the Tibetan Plateau from 1982 to 2020 - Gangfeng Zhang; Yaoyao Ma; Cesar Azorin-Molina; Lorenzo Minola; Yiwen Wang; Ziqi Lin; Heng Ma; Peijun Shi (Science of The Total Environment, 2025)

The oldest known Curvicubitidae (Hemiptera) from the Permian (Wuchiapingian) of Zhangshu City, Jiangxi Province, southern China - Qian-Qi Zhang; Lin Mu; Lei Zhang; Xu-Heng Du; Hai-Chun Zhang (Palaeoworld, 2025)

Volatility spillover between financial assets and transport energy - Zin Yau Heng; Boqiang Lin (Journal of Environmental Management, 2025)

Designation of multi-color and durable antimicrobial lyocell fiber by constructing various structural silver nanoparticles - Xiaofeng Wang; Wanjin Hu; Yonghao Zhou; Mengyao Cai; Xuelin Wang; Ke Lin; Chunhua Zhang; Sijie Zhou; Heng Pan; Lixin Du; Liangjun Xia (Chemical Engineering Journal, 2025)

Highly flexible Janus fabric based on TPU spraying and laser processing for personal thermal-wet management - Zixuan Xu; Yulun Wu; Shuqiang Min; Lin Hu; Tonghuan Zhan; Heng Wang; Yan Yuan; Haojun Luo; Yichen Tang; Bing Xu (Chemical Engineering Journal, 2025)

Recycling of sub-continental lithosphere during early ocean spreading revealed by Triassic trachytes in the central Tibetan Plateau - Zong-Yong Yang; Qiang Wang; Jun Wang; Lin Ma; Derek Wyman; Andrew C. Kerr; Xian-Wu Bi; Peng Sun; Xiu-Zheng Zhang; Lu-Lu Hao; Xiao Liu; Chuan-Bing Xu; et al. (Chemical Geology, 2025)

Lateral Cerebellar Theta Burst Stimulation Can Modulate Default Mode Network Connectivity in Autistic Adults - Hsing-Chang Ni; Heng Chien; Chun-Hung Yeh; Michael Cheng; Wei-Cheng Lin; Hsiang-Yuan Lin (The Cerebellum, 2025)

Coupled Vibration Response Analysis of Tension Leg Platform Tendon Under Irregular Ocean Wave Action - Qiangqiang Wu; Yinguang Du; Xiaofeng Luo; Tao Sun; Heng Lin (Journal of Marine Science and Engineering, 2025)
To analyze the dynamic response of tension leg platform (TLP) tendons under irregular ocean wave action, the governing equations of coupled vibration between the platform and tendon under irregular wave action are established based on Hamilton’s principle and the Kirchhoff hypothesis. Using the spectrum representation–random function method, the power spectral density function of the irregular wave load is derived, and the lateral wave forces at different tendon locations are calculated. The coupled lateral and axial responses of the tendon system are obtained through the fourth-order Runge–Kutta method. Considering the parametric vibrations of both the platform and tendon, the extreme lateral deflection of the tendon is employed as the control index to derive the probability density curves of the tendon deflection under irregular wave load. The results show that the amplitude of the wave load increases gradually along the height of the tendon, with a faster growth rate at locations closer to the water surface. The tendon’s lateral deflection response changes more drastically due to coupled parametric vibration of the platform. Based on 628 complete samples of irregular wave loads, the probability density curve and cumulative distribution curve of the extreme lateral deflection of the tendon under irregular wave loads are obtained. Under typical sea state conditions generated from the P-M wave spectrum, the reliability of the tendon under irregular wave load increases with the initial tension force.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Polystyrene/polylactic acid microplastics impair transzonal projections and oocyte maturation via gut microbiota-mediated lipoprotein lipase inhibition - Jiacheng Zhang; Hangqi Hu; Yutian Zhu; Xiyan Xin; Yuxin Jin; Qiancheng Zhao; Haolin Zhang; Dai Heng; Ze Ma; Xicheng Chai; Ruifan Lin; Yue Zhao; et al. (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Isolation, characterization, and biotechnological application of novel glutaminase-producing Bacillus strain for quality enhancement in soy sauce - Chen Siwei; Huang Jialiang; Liu Heng; Zhang Xiao; Xu Ting; Luo Lin; Chen Sui; Xu Zhenlin; Zhou Kai (Food Bioscience, 2025)

Interfacial water masking agent: Dynamic synergistic regulation of anode and cathode for ultra-long-life aqueous zinc metal batteries - Bin Xie; Chao Li; Min Li; Lieyuan Zhang; Zhaodan Fu; Yijia Luo; Gehong Su; Xin Tan; Heng Zhang; Qiaoji Zheng; Yu Huo; Jingxin Zhao; et al. (Chemical Engineering Journal, 2025)

Research on the mise-à-la-masse method based on multi-frequency pseudo-random signals: a case study in the Baiquan Spring region, Jinan, China - Yang Yang; Zhi-de Li; Heng Zhang; Lin Wang; Jia-feng Mi (Hydrogeology Journal, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Museomics and Salvaged Feathers Piece Together the Evolutionary History and Conservation Genomics of the Elusive, Critically Endangered Night Parrot ( Pezoporus occidentalis ) - Heng Lin Yeap; Gunjan Pandey; Jeremy J. Austin; John G. Oakeshott; Christopher M. Hardy; Stephen A. Murphy; Nicholas P. Leseberg; Allan H. Burbidge; Kenny J. Travouillon; Leo Joseph; Anna M. Kearns (Molecular Ecology, 2025)
The Night Parrot is a critically endangered nocturnal bird of Australia's arid zone. The species was “lost” for most of the 20th century until its rediscovery in 1990. Extant populations are now known in eastern and western Australia, but the species has been extirpated from much of its historical range. Here we estimate critically needed Essential Biodiversity Variables (EBVs) for the Night Parrot from historical and opportunistically collected contemporary samples. We find little population structure across the species' range and evidence of recent connectivity between extant populations ~2000 km apart. Most eastern individuals show significant kinship with one another, as did two from an extinct population in southern Australia. Heterozygosity is similarly low in all extant populations but ten‐fold lower in the extinct population sampled. Coalescent modelling of effective population size ( Ne ) suggests that Night Parrot numbers were reasonably high until around 90 years ago when Ne crashed from ~10,000 to ~100. Current Ne is now at its lowest in the past several million years. Our findings will help guide the ongoing management of one of Australia's most threatened birds.

Emergence and traceability of Salmonella enterica serotype Mbandaka harboring blaOXA-10 from chickens in China - Ke Wu; Jian Yang; Tiejun Zhang; Jing Zuo; Heng Lin; Juan Wang; Anyun Zhang; Changwei Lei; Hongning Wang (Veterinary Microbiology, 2025)

Prenatal exposure to air pollution and pediatric acute leukemia: A nationwide study - Hsin-Chien Yen; I-Chieh Chen; Wei-Szu Lin; Kuan-Chia Lin; Meng-Che Wu; Ching-Heng Lin (Science of The Total Environment, 2025)

Desulfurization wastewater evaporation for zero liquid discharge: Water and chloride balance in coal-fired power plants - Heng Chen; Hang Yu; Dayang Liang; Ziyan Yu; Liliang Lin; Ning Zhao; Linjun Yang (Journal of Water Process Engineering, 2025)

Identification of the sources and migration of antimony in karst terraces via Sb stable isotopes - Yunjie Wu; Guangyi Sun; Yu Lin; Xinyu Li; Yu Cheng; Heng Yao; Xinbin Feng (Journal of Hazardous Materials, 2025)

Mechanisms of endothelial senescence and vascular aging - Qiao Li; Zonghao Qian; Yuzhen Huang; Xiao Yang; Jiankun Yang; Nanyin Xiao; Guangyu Liang; Heng Zhang; Yanguang Fu; Yan Lin; Cuntai Zhang; Anding Liu (Biogerontology, 2025)

Halosimplex amylolyticum sp. nov., Halosimplex halobium sp. nov., Halosimplex marinum sp. nov., Halosimplex rarum sp. nov., Halovenus amylolytica sp. nov., Halovenus halobia sp. nov., and Halovenus marina sp. nov., halophilic archaea isolated from a marine tidal flat, a marine solar saltern, three coarse sea salts, and two saline lakes - Ya-Ling Mao; Shun Tan; Bei-Bei Wang; Xiao-Yan Yang; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Aminoguanidinium-engineered crater morphology in nanofiltration membranes: Unraveling transport mechanisms and structure-dependent purification performance - Xiaozhen Lu; Lin Wang; Xuewu Zhu; Liping Qiu; Heng Liang; Haiqing Chang; Daliang Xu; Xiaobin Tang; Jiashuai Wei; Bin Liu (Chemical Engineering Journal, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Microbiome and metabolome alterations in calves with enterohemorrhagic Escherichia coli and dyspeptic diarrhea - Lantian Huang; Zhengyu Lin; Xinyi Zhu; Long Guo; Luying Cui; Junsheng Dong; Kangjun Liu; Jianji Li; Heng Wang (Veterinary Microbiology, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Mitigating low-temperature frost damage in Taiwan high-altitude tea cultivation: physiological insight and protective strategies - Po-Heng Chen; Ru-Hong Lin; Chui-Feng Chiu; Yu-Sheng Lin (Planta, 2025)

Genome-based taxonomy of the family Haloarculaceae, proposal of Natronomonadaceae fam. nov., and description of four novel halophilic archaea from two saline lakes and a marine solar saltern - Ling-Rui Zhu; Ya-Ling Mao; Yao Hu; Ya-Ping Sun; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Comprehensive study of flusulfinam in paddy water–sediment microcosms: Enantioselective fate, degradation pathways, and toxicity assessment - Shiling Liu; Xiaoli Li; Siying Qin; Heng Zhang; Tengfei Zhang; Junqi Zhu; Lu Lin; Lei Lian; Fayang Xie; Huihua Tan; Feng Zhao (Journal of Hazardous Materials, 2025)

Asphalt pavement emission behavior under solar radiation during in-service period - Ming Jia; Hui Li; Xue Zhang; Ivan Miguel De Cachinho Cordeiro; Lin Bo; Guan Heng Yeoh (Journal of Hazardous Materials, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Correlation between the utilization of sodium-glucose cotransporter-2 (SGLT2) inhibitors and the risk of dementia: a nationwide population-based study in Taiwan - Wu-Lung Chuang; Stella Chin-Shaw Tsai; Yi-Chun Yang; Tsai-Ling Hsieh; Heng-Jun Lin; Yu-Han Huang; Fuu-Jen Tsai; Kuang-Hsi Chang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Impact of residual aluminum on nanofiltration gypsum scaling: Mitigation roles played by different species - Jinjin Jia; Daliang Xu; Jiaxuan Yang; Dachao Lin; Longfeng Hu; Wenxing Jin; Jinlong Wang; Weijia Gong; Guibai Li; Heng Liang (Water Research, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Decoding the Ediacaran Enigma: Gondwana paleogeography revisited through a provenance study of the Salt Range Formation (Salt Range, western Himalayas, Pakistan) - Waseem Khan; Licheng Wang; Eduardo Garzanti; Salman Ahmed Khattak; Abdus Saboor; Heng Peng; Lin Ding (Gondwana Research, 2025)

Halobellus marinus sp. nov., Halobellus ordinarius sp. nov., Halobaculum rarum sp. nov., and Halorarum halobium sp. nov., halophilic archaea isolated from marine solar salt and a saline lake - Ling-Rui Zhu; Chidiebele Nwankwo; Jing Hou; Heng-Lin Cui (Extremophiles, 2025)

Regulatory Roles of Exosomes in Aging and Aging-Related Diseases - Nanyin Xiao; Qiao Li; Guangyu Liang; Zonghao Qian; Yan Lin; Heng Zhang; Yangguang Fu; Xiao Yang; Cun-Tai Zhang; Jiankun Yang; Anding Liu (Biogerontology, 2025)

Establishing electro-functionalized gravity-driven ceramic membrane filtration (EGDCM) for decentralized treatment of algae-laden brackish water: Comparison of in-situ electro-oxidation and ex-situ electro-coagulation - Dachao Lin; Xinxu Shen; Caiwei Tan; Han Zhang; Rui Chen; Xing Du; Heng Liang (Water Research, 2025)

Interpretation of machine learning-based prediction models and functional metagenomic approach to identify critical genes in HBCD degradation - Yu-Jie Lin; Ping-Heng Hsieh; Chun-Chia Mao; Yang-Hsin Shih; Shu-Hwa Chen; Chung-Yen Lin (Journal of Hazardous Materials, 2025)

Improvement of stability and antioxidant capacity of peptide - iron complexes by sonication - Dong Lin; Yongqing Zhang; Qinqin Xiong; Liyun Zhang; Sha Cheng; Jia Yu; Mashaal Ahmad; Yalin Ni; Su Xu; Heng Luo (Food Chemistry, 2025)

Human milk oligosaccharides ameliorate intestinal barrier in aging honey bee by regulating gut microbiota - Xiaoya Lin; Yingying Lin; Yueyi Wang; Yujie Meng; Yafei Zhang; Heng Quan; Yao Lu; Hao Zheng; Huiyuan Guo (Food Bioscience, 2025)

Enhancing membrane distillation performance by adsorption using modified zeolite for shale gas produced water treatment - Haiqing Chang; Lin Huang; Mengzhe Lu; Zhongsen Yan; Pengwei Ji; Dan Qu; Fangshu Qu; Heng Liang (Desalination, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Cytotoxic monoterpenoid indole alkaloids from Tabernaemontana bovina - Bang-Yin Tan; Hua Lin; Heng-Gang Zhang; Jing-Zhi Zhao; Shi-Yu Deng; Rui-Rong Guo; Xin Wei; Lan-Chun Zhang; Rong-Ping Zhang; Hao-Fei Yu (Phytochemistry, 2025)

Seminal fluid proteins in the Queensland fruit fly: Tissue origins, effects of mating and comparative genomics - Khandaker Asif Ahmed; Heng Lin Yeap; Chris W. Coppin; Jian-Wei Liu; Gunjan Pandey; Phillip W. Taylor; Siu Fai Lee; John G. Oakeshott (Insect Biochemistry and Molecular Biology, 2025)

Indirect Z-scheme MXene@g-C3N4/MIL-101(Fe) heterojunction for the enhanced visible-light-responsive enrofloxacin photodegradation - Zhi-Fu Lin; Tzu-Heng Wang; Prashanth Venkatesan; Ruey-An Doong (Chemical Engineering Journal, 2025)

An involvement of a new zinc finger protein PbrZFP719 into pear self-incompatibility reaction - Ying Xu; Zhi-Heng Sui; Yi-Peng Ye; Lei Wu; Kai-Jie Qi; Min He; Lin Guo; Chao Gu; Shao-Ling Zhang (Plant Cell Reports, 2025)

Comprehensive Analyses of PANoptosome with Potential Implications in Cancer Prognosis and Immunotherapy - Yonghua Cai; Heng Xiao; Qixiong Zhou; Jie Lin; Xianqiu Liang; Wei Xu; Yongfu Cao; Xian Zhang; Hai Wang (Biochemical Genetics, 2025)
Cell death resistance significantly contributes to poor therapeutic outcomes in various cancers. PANoptosis, a unique inflammatory programmed cell death (PCD) pathway activated by specific triggers and regulated by the PANoptosome, possesses key features of apoptosis, pyroptosis, and necroptosis, but these cannot be accounted for by any of the three PCD pathways alone. While existing studies on PANoptosis have predominantly centered on infectious and inflammatory diseases, its role in cancer malignancy has been understudied. In this comprehensive investigation, we conducted pan-cancer analyses of PANoptosome component genes across 33 cancer types. We characterized the genetic, epigenetic, and transcriptomic landscapes, and introduced a PANoptosome-related potential index (PANo-RPI) for evaluating the intrinsic PANoptosome assembly potential in cancers. Our findings unveil PANo-RPI as a prognostic factor in numerous cancers, including KIRC, LGG, and PAAD. Crucially, we established a significant correlation between PANo-RPI and tumor immune responses, as well as the infiltration of diverse lymphoid and myeloid cell subsets across nearly all cancer types. Moreover, a high PANo-RPI was consistently associated with improved immunotherapy response and efficacy, as evidenced by re-analysis of multiple immunotherapy cohorts. In conclusion, our study suggests that targeting PANoptosome components and modulating PANoptosis may hold tremendous therapeutic potential in the context of cancer.

Natronorarus salvus gen. nov., sp. nov., Halalkalicoccus ordinarius sp. nov., and Halalkalicoccus salilacus sp. nov., halophilic archaea from a soda lake and two saline lakes, and proposal to classify the genera Halalkalicoccus and Natronorarus into Halalkalicoccaceae fam. nov. in the order Halobacteriales within the class Halobacteria - Ya-Ling Mao; Xin-Yue Dong; Cong-Qi Tao; Zhang-Ping Wu; Xiao-Wei Shi; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2025)

Gestational exposure to carbon black nanoparticles triggered fetal growth restriction in mice: The mediation of inactivating autophagy-lysosomal degradation system in placental ferroptosis - Jing Li; Hongying Gao; Zehua Xu; Biling Gao; Liang Zhang; Bowen Su; Shijing Yang; Jiangling Liu; Ya Liu; Xiuxiu Wang; Heng Wang; Yi Lin; et al. (Science of The Total Environment, 2025)

Distinct ultrafast dynamics of bilayer and trilayer nickelate superconductors regarding the density-wave-like transitions - Yidian Li; Yantao Cao; Liangyang Liu; Pai Peng; Hao Lin; Cuiying Pei; Mingxin Zhang; Heng Wu; Xian Du; Wenxuan Zhao; Kaiyi Zhai; Xuefeng Zhang; et al. (Science Bulletin, 2025)

The returns-connectedness between environment, social, and governance funds and biofuels - Zin Yau Heng; Boqiang Lin (Journal of Environmental Management, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Synergistic effect of probiotics and postbiotics on reducing cytokine storm, lung dysfunction, and immune escape phenomenon caused by SARS-CoV-2 infection - Yi-Heng Chiu; Hung-Pin Chiu; Meei-Yn Lin (Food Bioscience, 2025)

UAV-Based Simulation of 3D Random Discontinuity Networks in Rock Slopes - Na Chen; Zhi-Wei Liu; Heng-Lin Xiao; Li-Hua Li (Geotechnical and Geological Engineering, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Environmental contamination and risks of organic UV filters: Source, discharge, analytical methods and implications for ecological and human health - Yue-hong Sun; Heng-Yu Wu; Feng-Qi Xie; Jia-Ru Ma; Qin-Lin Tang; Yan-Fen Chen; Hao Li; You-Sheng Liu; Guang-Guo Ying (Science of The Total Environment, 2024)

Discovery of the Callovian Oceanic Anoxic Event in the Qiangtang Basin, eastern Tethys: Insights from in situ calcite U Pb dating - Licheng Wang; Eduardo Garzanti; Heng Peng; Yalin Li; Lijian Shen; Songlin He; Yahui Yue; Waseem Khan; Lin Ding (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

Corrigendum to “Revisiting the formation of lunar anorthosites via the Rb-Sr isotope systematics” [Lithos, volume 486–487, (2024) 107780] - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Effects of pre-chlorination on ultrafiltration process in directly treating seasonal high-turbidity surface water: Membrane fouling control and shock load resisting - Haochun Wang; Yaru Zhang; Chenghai Lin; Ao Wang; Yanrui Wang; Yating Hu; Shu Jiang; Jinlong Wang; Heng Liang; Xiaobin Tang (Journal of Water Process Engineering, 2024)

Impacts of distinct residual aluminum on gypsum scaling in nanofiltration: Identification of key species - Jinjin Jia; Jinlong Wang; Dachao Lin; Jing Zhao; Hesong Wang; Longfeng Hu; Jiaxuan Yang; Han Zhang; Guibai Li; Heng Liang (Desalination, 2024)

Electron-deficient wastewater treatment in membrane-aerated conductive biofilm reactor: Performance and mechanism - Weijia Gong; Han Zhang; Minghao Xue; Lin Guo; Mengmeng Jiang; Yuzhou Zhao; Heng Liang (Bioresource Technology, 2024)

Genome-Based Classification of ‘Haloarcula aidinensis’ and Description of Three Novel Halophilic Archaea Isolated from an Inland Saline Lake, Coastal Saline Soil, and a Marine Solar Saltern - Xue Ma; Yao Hu; Jing Hou; Yu-Guang Zhou; Heng-Lin Cui (Current Microbiology, 2024)

Genome‑based classification of the family Natrialbaceae and description of four novel halophilic archaea from three saline lakes and a saline-alkaline land - Xin-Yue Dong; Ya-Ling Mao; Qing-Ke Zhang; Ling-Rui Zhu; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Correction: Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Genome-based classification of genera Halosegnis and Salella, and description of four novel halophilic archaea isolated from a tidal flat - Yao Hu; Xue Ma; Shun Tan; Xin-Xin Li; Mu Cheng; Jing Hou; Heng-Lin Cui (Antonie van Leeuwenhoek, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Human activities exacerbate river network degrading in the Qinhuai River basin - Yue-yang Dong; Peng Wang; Zu-lin Hua; Shan-heng Huang (Science of The Total Environment, 2024)

Burden of biliary tract carcinoma in China (1990–2021): Findings from the 2021 Global Burden of Disease Study - Wei Zhang; Yi-Jun Wang; Jiang-Mei Liu; Xu-Heng Sun; Yan Jiang; Fang Shen; Li-Juan Shen; Jing Xiang; Jun-Feng Zhang; Lin-Hua Yang; Wen-Guang Wu; Tao Chen; et al. (Science Bulletin, 2024)

Revisiting the formation of lunar anorthosites via the Rb Sr isotope systematics - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Multiple modulating energy-efficient nanofiltration membranes during high-quality drinking water towards high mineral/organic matter selectivity - Xiaozhen Lu; Bin Liu; Xuewu Zhu; Lin Wang; Haiqing Chang; Zhe Yang; Daliang Xu; Ruoxi Wu; Fulin Shao; Jingtao Xu; Heng Liang (Desalination, 2024)

Input panel for handwriting detection based on triboelectric nanogenerator - Zhigang Peng; Wandi Chen; Jianpu Lin; Haonan Wang; Heng Tang; Yu Zhang; Tailiang Guo; Xiongtu Zhou; Chaoxing Wu; Yongai Zhang (Chemical Engineering Journal, 2024)

Carbonate system in the subtropical Jiulong River Estuary and CO2 flux estimation under modulation of tidal cycle - Weicong Chen; Heng Sun; Zhongyong Gao; Jiaming Lin; Min Xu; Aijun Wang; Shuqin Tao (Acta Oceanologica Sinica, 2024)

Mode-dependent supervisory switching fault-tolerant control for dynamic positioning ships with actuator faults - Heng Li; Xiaogong Lin (Ocean Engineering, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Hydroxyl radical mediated extracellular degradation of tetracycline under aerobic and anaerobic conditions stimulated by bio-FeS nanoparticles - Huixia Lan; Ke Li; Qiliang Cao; Qiaochu Liang; Yecheng Lin; Veeriah Jegatheesan; Binghua Yan; Heng Zhang; Yang Zhang (Journal of Hazardous Materials, 2024)

Zn-Mn bimetallic oxide derived from waste battery to activate peroxymonosulfate for bisphenol A removal under visible light irradiation - Ziren Wang; Yahui Ma; Heng Lin; Liting Luo; Hui Zhang (Journal of Environmental Chemical Engineering, 2024)

Influence and mechanism of typical transition metal ions on the denitrification performance of heterotrophic nitrification-aerobic denitrification bacteria - Yun-chun Shi; Fan Gou; Ai-ling Chen; Zhi-lin Xing; Qian Zhang; Heng Wu; Tian-tao Zhao (Environmental Research, 2024)

Long non-coding RNA MAGEA4-AS1 binding to p53 enhances MK2 signaling pathway and promotes the proliferation and metastasis of oral squamous cell carcinoma - Xiaoxiao Wei; Zhangfu Li; Heng Zheng; Xiaolian Li; Yuntao Lin; Hongyu Yang; Yuehong Shen (Functional & Integrative Genomics, 2024)

Sex-Specific Associations of Five Serum Essential Metal Elements with Thyroid Nodules in Euthyroid Adults: a Cross‑sectional Study - Qintao Ma; Ying Li; Genfeng Yu; Siyang Liu; Yuqi Jiang; Hualin Duan; Dongmei Wang; Yajun He; Xingying Chen; Nanfang Yao; Xu Lin; Heng Wan; et al. (Biological Trace Element Research, 2024)

Organophosphate esters (OPEs) pollution characteristics, bioaccumulation and human consumption implication in wild marine organisms from the Yellow River Estuary, China - Jianing Lin; Xinshu Ding; Jinzeng Gu; Lutao Zhang; Jinyu Chao; Heng Zhang; Song Feng; Changsheng Guo; Jian Xu; Zhenhui Gao (Marine Pollution Bulletin, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

A hyperstable, low-salt adapted protease from halophilic archaeon with potential applications in salt-fermented foods - Jing Hou; Qing-Ke Zhang; Ruo-Yao Zhang; Si-Ya Li; Yuan-Yiyi Liu; Heng-Lin Cui (Food Research International, 2024)

High-performance Chinese ink flower-shaped evaporator: Intensified heat through light concentration to achieve water-energy balance - Jinbu Su; Yunong Xie; Heng Zhao; Yuyi Xu; Xuli Lin; Chenyi Shi; Xiaoyu Cao; Chengbing Wang (Chemical Engineering Journal, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Deciphering spatial-temporal dynamics of flood exposure in the United States, - Joynal Abedin; Lei Zou; Mingzheng Yang; Robert Rohli; Debayan Mandal; Yi Qiang; Humaira Akter; Bing Zhou; Binbin Lin; Heng Cai (Sustainable Cities and Society, 2024)

Study on Plant-blanket to reduce heavy metal migration caused by precipitation and to improve the soil environment of pyritic tailings - Kangkai Lin; Jiannan Jian; Yumei Zhang; Yikai Liu; Shiyao Li; Yun Zhao; Heng Xu (Science of The Total Environment, 2024)

Carbon dioxide-focused greenhouse gas emissions from petrochemical plants and associated industries: Critical overview, recent advances and future prospects of mitigation strategies - Yuxin Yan; Yoong Xin Pang; Xiang Luo; Qingyang Lin; Cheng Heng Pang; Honglei Zhang; Xiang Gao; Tao Wu (Process Safety and Environmental Protection, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

Unveiling community adaptations to extreme heat events using mobile phone location data - Hao Tian; Heng Cai; Leiqiu Hu; Yi Qiang; Bing Zhou; Mingzheng Yang; Binbin Lin (Journal of Environmental Management, 2024)

LithoSegNet: Regional attention-based deep fusion of multi-scale and cross-stage features for real-time lithology segmentation - ZhenHao Xu; Heng Shi; Peng Lin; Shan Li (International Journal of Rock Mechanics and Mining Sciences, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

Unveiling the structural properties and induced resistance activity in rice of Chitin/Chitosan-Glucan Complex of Rhizoctonia solani AG1 IA inner cell wall - Hui Gu; Jie Qin; Jinxuan Wen; Yudie Lin; Xiaochen Jia; Wenxia Wang; Heng Yin (Carbohydrate Polymers, 2024)

MSC-Derived Extracellular Vesicles Alleviate NLRP3/GSDMD-Mediated Neuroinflammation in Mouse Model of Sporadic Alzheimer’s Disease - Lishan Lin; Longxin Huang; Sen Huang; Weineng Chen; Heng Huang; Li Chi; Fengjuan Su; Xiaoqing Liu; Kang Yuan; Qiuhong Jiang; Changu Li; Wanli W. Smith; et al. (Molecular Neurobiology, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Halobacterium yunchengense sp. nov., Natronomonas amylolytica sp. nov., Halorientalis halophila sp. nov., Halobellus salinisoli sp. nov., halophilic archaea isolated from a saline lake and inland saline soil - Ling Cui; Yao Hu; Xin-Xin Li; Xue Ma; Mu Cheng; Shun Tan; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Genome-based classification of the family Haloferacaceae and description of five novel species of Halobaculum - Shun Tan; Ling-Rui Zhu; Qing-Ke Zhang; Xin-Yue Dong; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

A new phenylpropanoic acid congener from Zanthoxylum nitidum - Feng Qin; Li Luo; Yao Chen; Gang Wei; Chun-Ce Wei; Xiao-Hua Yang; Yi-Lin Fang; Heng-Shan Wang (Natural Product Research, 2024)

Confined-immigration enhances water resistance and weatherability of highly transparent coatings for cultural heritage preservation - Lin Chen; Heng Zhang; Shilei Zhu; Zhuangzhuang Li; Wenwen Yu; Fengbo Zhu; Ya Nan Ye; Qiang Zheng (Chemical Engineering Journal, 2024)

Halomarina litorea sp. nov., Halomarina pelagica sp. nov., Halomarina halobia sp. nov., and Halomarina ordinaria sp. nov., Halophilic Archaea Isolated from Coastal and Inland Saline Soil - Mu Cheng; Xin-Xin Li; Jing Hou; Heng-Lin Cui (Current Microbiology, 2024)

Effects of luteolin supplementation on growth, histology, antioxidant capacity, non−specific immunity and intestinal microbiota of the red swamp crayfish (Procambarus clarkii) - Yanbin Lin; Shengxuan Li; Yulong Li; Liu Fang; Heng Zhang; Qian Wang; Guoliang Ruan (Animal Feed Science and Technology, 2024)

RETRACTED: A systematic review of antibiotics and antibiotic resistance genes (ARGs) in mariculture wastewater: Antibiotics removal by microalgal-bacterial symbiotic system (MBSS), ARGs characterization on the metagenomic - Weijia Gong; Lin Guo; Chenxin Huang; Binghan Xie; Mengmeng Jiang; Yuzhou Zhao; Haotian Zhang; YuXuan Wu; Heng Liang (Science of The Total Environment, 2024)

Event-driven prescribed performance distributed formation control for MSVs based on second-order step response with actuator input saturation - Chonglang Lai; Heng Li; Xiaogong Lin (Ocean Engineering, 2024)

Thiol-functionalized black carbon as effective and economical materials for Cr(VI) removal: Simultaneous sorption and reduction - Kamonchanok Huangmee; Liang-Ching Hsu; Yu-Min Tzou; Yen-Lin Cho; Chih-Hao Liao; Heng Yi Teah; Yu-Ting Liu (Journal of Environmental Management, 2024)

Production of novel mung bean peptides-based zinc supplement: Process optimization, chelation mechanism, and stability assessment in vitro - Liyun Zhang; Yinxia Wang; Yalin Ni; Yongqing Zhang; Yongling Liu; Bin Du; Heng Luo; Dong Lin (Food Bioscience, 2024)

Systematic engineering for efficient production of nicotinamide mononucleotide from d-xylose and nicotinamide in Escherichia coli - Chang Su; Lin Cheng; Jin-Song Gong; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2024)

Intrinsically stretchable jellyfish-like gold nanowires film as multifunctional wearable chemical and physical sensors - Heng Zhang; Fenge Lin; Gangsheng Chen; Cheng Yang; Hanqiang Zhang; Mengwen Yan; Heng Li; Xi Wang; Wenlong Cheng; Yi Chen (Chemical Engineering Journal, 2024)

Neuropsychiatric comorbidities in tuberous sclerosis complex patients with epilepsy: results of the TAND checklist survey - Hom-Yi Lee; Chien-Heng Lin; Xing-An Wang; Jeng-Dau Tsai (Acta Neurologica Belgica, 2024)

Wavelength dependency and photosensitizer effects in UV-LED photodegradation of iohexol - Meng-Yuan Xu; Chao Zeng; Yi-Li Lin; Tian-Yang Zhang; Qi Fu; Heng-Xuan Zhao; Zhen-Ning Luo; Zheng-Xiong Zheng; Tong-Cheng Cao; Chen-Yan Hu; Bin Xu (Water Research, 2024)

Halomontanus rarus gen. nov., sp. nov., a novel halophilic archaeon of the family Natrialbaceae from salt lakes on the Qinghai-Xizang Plateau - Ya-Ling Mao; Bei-Bei Wang; Xue-Meng Yin; Jing Hou; Heng-Lin Cui (Systematic and Applied Microbiology, 2024)

Selenium in plants: A nexus of growth, antioxidants, and phytohormones - Sufian Ikram; Yang Li; Chai Lin; Debao Yi; Wang Heng; Qiang Li; Lu Tao; Yu Hongjun; Jiang Weijie (Journal of Plant Physiology, 2024)

Sustainable production of biodiesel enabled by acid-base bifunctional ZnF2 via one-pot transformation of Koelreuteria integrifoliola oil: Process optimization, kinetics study and cost analysis - Baohong Zheng; Lin Ban; Yingxia Nie; Long Chen; Song Yang; Heng Zhang (Journal of Cleaner Production, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Identification and quantification of microplastics in salts by complementary approaches using pyrolysis-gas chromatography/quadrupole-time of flight mass spectrometry (Py-GC/QTOFMS) and laser direct infrared (LDIR) chemical imaging analysis - Hongying Gao; Heng Wang; Yuchao Wang; Yi Lin; Jianbo Yan; Heqing Shen (Environmental Pollution, 2024)

CFD simulation of pumping ventilation with two asymmetrically arranged openings on the rear wall in a three-story isolated building - Huai-Yu Zhong; Jie Sun; Chao Lin; Hideki Kikumoto; Wei Dong; Yang Cai; Fu-Yun Zhao; Song-Heng Wu; Fu-Ping Qian (Building and Environment, 2024)

SeisGAN: Improving Seismic Image Resolution and Reducing Random Noise Using a Generative Adversarial Network - Lei Lin; Zhi Zhong; Chuyang Cai; Chenglong Li; Heng Zhang (Mathematical Geosciences, 2024)

Single-cell profile reveals the landscape of cardiac immunity and identifies a cardio-protective Ym-1hi neutrophil in myocardial ischemia–reperfusion injury - Yalan Dong; Zhenyu Kang; Zili Zhang; Yongqiang Zhang; Haifeng Zhou; Yanfei Liu; Xinxin Shuai; Junyi Li; Liangqingqing Yin; Xunxun Wang; Yan Ma; Heng Fan; et al. (Science Bulletin, 2024)

Robust fault-tolerant control for dynamic positioning of ships with prescribed performance - Heng Li; Xiaogong Lin (Ocean Engineering, 2024)

Whole-genome sequencing of Escherichia coli from retail meat in China reveals the dissemination of clinically important antimicrobial resistance genes - Qin Wang; Ying-Yue Han; Tie-Jun Zhang; Xuan Chen; Heng Lin; Hong-Ning Wang; Chang-Wei Lei (International Journal of Food Microbiology, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Photochemical oxidation of VOCs and their source impact assessment on ozone under de-weather conditions in Western Taiwan - Manisha Mishra; Pin-Hsin Chen; Guan-Yu Lin; Thi-Thuy-Nghiem Nguyen; Thi-Cuc Le; Racha Dejchanchaiwong; Perapong Tekasakul; Shih-Heng Shih; Ciao-Wei Jhang; Chuen-Jinn Tsai (Environmental Pollution, 2024)

Cellulose nanofibers embedded chitosan/tannin hydrogel with high antibacterial activity and hemostatic ability for drug-resistant bacterial infected wound healing - Dangwei Li; Xiangyang Dong; Xia Liu; Heng Lin; Di Yang; Xiaowen Shi; Chaoji Chen; Fenghua Tao; Linbin Jiang; Hongbing Deng (Carbohydrate Polymers, 2024)

Genome-based taxonomy of genera Haloarcula and Halomicroarcula, and description of six novel species of Haloarcula - Xue Ma; Yao Hu; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Halorubrum hochsteinianum sp. nov., an ancient haloarchaeon from a natural experiment - Russell H. Vreeland; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2024)

Main effects and interactions of multiple key factors related to thermal perception - Yuxin Yang; Junmeng Lyu; Heng Du; Zhiwei Lian; Weiwei Liu; Lin Duanmu; Yongchao Zhai; Bin Cao; Yufeng Zhang; Xiang Zhou; Zhaojun Wang; Xiaojing Zhang; et al. (Science of The Total Environment, 2024)

Beneficiation of silver and silver-bearing lead–zinc ores: A review - Hongliang Zhang; Heng Yu; Wei Sun; Shangyong Lin; Chenyang Zhang (Minerals Engineering, 2024)

Submicron spatial resolution Pb-Pb dating for the formation age of Chang'e-5 basalt - Jia-Long Hao; Wei Yang; Hui-Cun He; Di Zhang; Sen Hu; Heng-Ci Tian; Rui-Ying Li; Yang-Ting Lin (Lithos, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Thermally managed and fireproof composite aerogels for safer and year-round energy saving - Wei Cai; Zhaoxin Li; Heng Xie; Wei Wang; Tianyang Cui; Bicheng Lin; Liangyuan Qi; Xin Hu; Yu Du; Yang Ming; Shuo Shi; Daming Chen; et al. (Chemical Engineering Journal, 2024)

Prognostic significance and immune escape implication of tumor-infiltrating neutrophil plasticity in human head and neck squamous cell carcinoma - Xiaoke Zhu; Yu Heng; Duo Zhang; Di Tang; Jian Zhou; Hanqing Lin; Jingyu Ma; Xuping Ding; Lei Tao; Liming Lu (Human Cell, 2024)

Experimental and theoretical study on longitudinal deformation and internal force of shield tunnel under surcharge - Zhi Ding; Xiao Zhang; Shao-Heng He; Yong-Jie Qi; Cun-Gang Lin (Tunnelling and Underground Space Technology, 2024)

Comparison of four pre-oxidants coupled powdered activated carbon adsorption for odor compounds and algae removal: Kinetics, process optimization, and formation of disinfection byproducts - Heng-Xuan Zhao; Shuang Zhang; Tian-Yang Zhang; Yi-Ping Zhu; Ren-Jie Pan; Meng-Yuan Xu; Zheng-Xiong Zheng; Chen-Yan Hu; Yu-Lin Tang; Bin Xu (Science of The Total Environment, 2024)

First classification of iron meteorite fragment preserved in Chang’e-5 lunar soils - Xiaoying Liu; Lixin Gu; Heng-Ci Tian; Jing Li; Xu Tang; Sen Hu; Yangting Lin (Science Bulletin, 2024)

Water-ultrastable perovskite CsPbBr3 nanocrystals tailored by surface-confined strategy for amaranth sensing in food samples - Lei Hu; Kai-Qi Liu; Feng Li; Heng-Ye Li; Wei Wang; Hai-Lin Fang; Hang Gao; Zhong-Xia Wang (Food Chemistry, 2024)

Lithium and oxygen isotopic constraints on the source and evolution of ore-forming fluids: a case study from the Shuiyindong Carlin-type gold deposit, SW China - Ningning Hu; Ruizhong Hu; Heng Chen; Shanling Fu; Jiehua Yang; Lin Xu; Chongguang Luo (Mineralium Deposita, 2024)

Waterlogging influences the physiology index and antioxidant enzyme activity in Cucurbita maxima and Cucurbita moschata - Kuan-Hung Lin; Shi-Peng Chen; Yi-Ru Su; Yi-Heng Tsai; Hsin-Hung Lin (Horticulture, Environment, and Biotechnology, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Prolonged Exposure to Plant Volatiles does not Significantly Affect Pban Expression and Mating Behavior in Diamondback Moth [Plutella Xylostella (Lepidoptera: Plutellidae)] - Houjun Tian; Ruibin Xu; Heng Li; Shuo Lin; Yixin Chen; Yong Chen; Guang Yang; Hui Wei (Journal of Chemical Ecology, 2024)

Positive impacts of dietary prebiotic inulin on growth performance, antioxidant capacity, immunity, and intestinal microbiota of red swamp crayfish (Procambarus clarkii) - Qian Wang; Yanbin Lin; Heng Zhang; Wenhao Fan; Shengxuan Li; Guoliang Ruan; Liu Fang (Aquaculture International, 2024)

Ozone containment through selective mitigation measures on precursors of volatile organic compounds - Sheng-Po Chen; Wen-Tzu Liu; Fang-Yi Cheng; Chieh-Heng Wang; Shih-Ming Huang; Jia-Lin Wang (Science of The Total Environment, 2024)

Ammonia release characteristics during desulfurization wastewater evaporation: Mechanisms and implications - Heng Chen; Dawei Hou; Zhihao Li; Lingxiao Zhan; Lijian Jin; Suoqi Zheng; Yurui Wang; Hao Wu; Ning Zhao; Liliang Lin; Linjun Yang (Journal of Water Process Engineering, 2024)

Highly effective degradation of ibuprofen by alkaline metal-doped copper oxides via peroxymonosulfate activation: Mechanisms, degradation pathway and toxicity assessments - Meng-Wei Zheng; Cheng-Wei Lin; Pei-Hsin Chou; Chao-Lung Chiang; Yan-Gu Lin; Shou-Heng Liu (Journal of Hazardous Materials, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Changes in properties of human milk under different conditions of frozen storage - Kaibo Wang; Yanfeng Zhao; Sijia Song; Yingying Lin; Yujia Luo; Yafei Zhang; Yi Xue; Wusun Li; Yuning Zhang; Yao Lu; Heng Quan; Hao Zhang; et al. (Food Research International, 2024)

In-situ repairing quantum-dot-monolayer-film defects for laminated light-emitting diodes - Heng Lin; Yang Liu; Hailong Hu; Tailiang Guo; Fushan Li (Chemical Engineering Journal, 2024)

Mineral scaling induced membrane wetting in membrane distillation for water treatment: Fundamental mechanism and mitigation strategies - Haiqing Chang; Yingyuan Zhu; Lin Huang; Zhongsen Yan; Fangshu Qu; Heng Liang (Water Research, 2023)

Mixed chlorine/chloramines in disinfected water and drinking water distribution systems (DWDSs): A critical review - Renjie Pan; Tian-Yang Zhang; Huan He; Zheng-Xiong Zheng; Zheng-Yu Dong; Heng-Xuan Zhao; Meng-Yuan Xu; Zhen-Ning Luo; Chen-Yan Hu; Yu-Lin Tang; Mohamed Gamal El-Din; Bin Xu (Water Research, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

New insights into the influence of pre-oxidation on membrane fouling during nanofiltration of brackish water considering inorganic-organic complexation and oxidant reduction byproducts - Dachao Lin; Han Zhang; Zhihong Wang; Daliang Xu; Guibai Li; Mathias Ulbricht; Heng Liang (Science of The Total Environment, 2023)

Exploring the applications of carbon dioxide radical anion in organic synthesis - Yong-Yuan Gui; Si-Shun Yan; Wei Wang; Lin Chen; Wei Zhang; Jian-Heng Ye; Da-Gang Yu (Science Bulletin, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Modeling of errors resulting from vehicle motions for CHZII mobile gravimeter and its performance verification during marine surveys - Hai-bo Tu; Jian-gang He; Ming Hu; Xing-hui Liang; Lei-jun Liu; Qin-qin Dong; Sun-jun Liu; Hui Zhang; Yong-tao Fu; Jun-jian Lang; Heng Sun; Lin-tao Liu (Applied Geophysics, 2023)

Silica wastes derived multifunctional coatings for formaldehyde photodegradation and autonomous indoor humidity buffering - Yu-Rou Lin; Meng-Wei Zheng; Shou-Heng Liu (Chemosphere, 2023)

Reassessing the classification of Chang'e-5 basalts using pyroxene composition - Heng-Ci Tian; Wei Yang; Yubing Gao; Qing Zhou; Renhao Ruan; Yangting Lin; Xianhua Li; Fuyuan Wu (Lithos, 2023)

An operational approach for large-scale mapping of water clarity levels in inland lakes using landsat images based on optical classification - Shijiao Lu; Yingchun Bian; Fangfang Chen; Jie Lin; Heng Lyu; Yunmei Li; Huaiqing Liu; Yang Zhao; Yiling Zheng; Linze Lyu (Environmental Research, 2023)

Janus MXene-based photothermal membrane for efficient and durable water evaporation - Jinbu Su; Yunong Xie; Pengkui Zhang; Rui Yang; Boli Wang; Heng Zhao; Yuyi Xu; Xuli Lin; Jing Shi; Chengbing Wang (Desalination, 2023)

Global analysis approach of stability of deep foundation pit slopes reinforced by underground diaphragm walls and prestressed anchor cables - Heng Kong; Miao Dong; Xitailang Cao; Shan Lin; ShuaiXing Zhao; Hong Zheng (Computers and Geotechnics, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Prospects and perspectives on advanced materials for sodium-ion batteries - Zhen-Yi Gu; Xiao-Tong Wang; Yong-Li Heng; Kai-Yang Zhang; Hao-Jie Liang; Jia-Lin Yang; Edison Huixiang Ang; Peng-Fei Wang; Ya You; Fei Du; Xing-Long Wu (Science Bulletin, 2023)

Effects of ammonia on combustion of coal in stoichiometric premixed methane–air flames - Yueh-Heng Li; Bo-Cheng Chuang; Po-Hung Lin; Janusz Lasek (Fuel, 2023)

An in-situ grown high-efficiency Zn-terephthalate metal–organic framework/ZnO hybrid interface protection layer to achieve highly reversible dendrite-free Zn anodes - Pingli Wu; Yi Cao; Heng Cao; Yu Liu; Xiaomin Huang; Jialin Zhang; Yang Cao; Yujia Long; Yijun Zhai; Zhuang Wu; Qiaoji Zheng; Dunmin Lin (Chemical Engineering Journal, 2023)

Benzeneboronic−alginate/quaternized chitosan−catechol powder with rapid self-gelation, wet adhesion, biodegradation and antibacterial activity for non-compressible hemorrhage control - Yan Du; Xingtao Chen; Lin Li; Heng Zheng; Aiping Yang; Hong Li; Guoyu Lv (Carbohydrate Polymers, 2023)

Association of Ferroptosis with Severity and Outcomes in Acute Ischemic Stroke Patients Undergoing Endovascular Thrombectomy: A Case-control Study - Shin-Joe Yeh; Chih-Hao Chen; Yen-Heng Lin; Li-Kai Tsai; Chung-Wei Lee; Sung-Chun Tang; Jiann-Shing Jeng (Molecular Neurobiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Continuous extensional uplift controls the Silurian structural evolution of the Sichuan Basin, southwest China - Gen Li; Zhong-Quan Li; Dian Li; Heng-Lin Liu; Shan Yan; Gui-Ping Su; Xing-Wang Tian (Marine and Petroleum Geology, 2023)

Optimization and performance characteristics of diesel engine using green fuel blends with nanoparticles additives - Ching-Ming Lai; Dong Lin Loo; Yew Heng Teoh; Heoy Geok How; Thanh Danh Le; Huu Tho Nguyen; Ayman A. Ghfar; Farooq Sher (Fuel, 2023)

Honey bee foraging ability suppressed by imidacloprid can be ameliorated by adding adenosine - Yu-Chun Lin; Yun-Heng Lu; Cheng-Kang Tang; En-Cheng Yang; Yueh-Lung Wu (Environmental Pollution, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

A Self-attention Graph Convolutional Network for Precision Multi-tumor Early Diagnostics with DNA Methylation Data - Xue Jiang; Zhiqi Li; Aamir Mehmood; Heng Wang; Qiankun Wang; Yanyi Chu; Xueying Mao; Jing Zhao; Mingming Jiang; Bowen Zhao; Guanning Lin; Edwin Wang; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Harnessing split fluorescent proteins in modular protein logic for advanced whole-cell detection - Ping-Heng Lin; Ssu-Tzu Tsai; Yu-Chia Chang; Yi-Ju Chou; Yi-Chun Yeh (Analytica Chimica Acta, 2023)

Persulfate promoted visible photocatalytic elimination of bisphenol A by g-C3N4–CeO2 S-scheme heterojunction: The dominant role of photo-induced holes - Yin Xu; Xin Tang; Yan Xiao; Huiling Tang; Heng Lin; Yujuan Lv; Hui Zhang (Chemosphere, 2023)

miR-665 overexpression inhibits the apoptosis of luteal cells in small ruminants suppressing HPGDS - Heng Yang; Lin Fu; Licai Li; Dezhi Zhang; Qianyong Li; Peng Zhou (Theriogenology, 2023)

Salinilacihabitans rarus gen. nov., sp. nov., Natrononativus amylolyticus gen. nov., sp. nov., Natronobeatus ordinarius gen. nov., sp. nov., and Halovivax gelatinilyticus sp. nov., halophilic archaea, isolated from a salt lake and soda lakes - Xin-Xin Li; Shun Tan; Mu Cheng; Yao Hu; Xue Ma; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Insight into mixed chlorine/chloramines conversion and associated water quality variability in drinking water distribution systems - Renjie Pan; Tian-Yang Zhang; Zheng-Xiong Zheng; Jian Ai; Tao Ye; Heng-Xuan Zhao; Chen-Yan Hu; Yu-Lin Tang; Jing-Jing Fan; Bing Geng; Bin Xu (Science of The Total Environment, 2023)

Yeast biomass ornamented macro-hierarchical chitin nanofiber aerogel for enhanced adsorption of cadmium(II) ions - Iqra Shahzadi; Yang Wu; Heng Lin; Jing Huang; Ze Zhao; Chaoji Chen; Xiaowen Shi; Hongbing Deng (Journal of Hazardous Materials, 2023)

Simultaneously optimizing radiative decay and up-conversion of triphenylamine-based thermally activated delayed fluorescence emitters to achieve efficient deep-red organic light-emitting diodes - Hao-Yu Yang; Heng-Yuan Zhang; Ming Zhang; Hao Zhuo; Hui Wang; Hui Lin; Si-Lu Tao; Cai-Jun Zheng; Xiao-Hong Zhang (Chemical Engineering Journal, 2023)

Growth of spiral ganglion neurons induced by graphene oxide/oxidized bacterial cellulose composite hydrogel - Lin Shi; Guodong Hong; Chuntao Chen; Xueqian Li; Heng Zhang; Renjie Chai; Dongping Sun (Carbohydrate Polymers, 2023)

Evaluation of key factors influencing urban ozone pollution in the Pearl River Delta and its atmospheric implications - Xiao-Yu Lin; Shi-Yong Xia; Yao Luo; Heng-Xiao Han; Ling-Yan He (Atmospheric Environment, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Inpainting truncated areas of CT images based on generative adversarial networks with gated convolution for radiotherapy - Kai Xie; Liugang Gao; Heng Zhang; Sai Zhang; Qianyi Xi; Fan Zhang; Jiawei Sun; Tao Lin; Jianfeng Sui; Xinye Ni (Medical & Biological Engineering & Computing, 2023)

Environmental quality mediates the ecological dominance of cooperatively breeding birds - Yu‐Heng Lin; Ying‐Yu Chen; Dustin R. Rubenstein; Ming Liu; Mark Liu; Sheng‐Feng Shen (Ecology Letters, 2023)
Although social species as diverse as humans and ants are among the most abundant organisms on Earth, animals cooperate and form groups for many reasons. How these different reasons for grouping affect a species' ecological dominance remains unknown. Here we use a theoretical model to demonstrate that the different fitness benefits that animals receive by forming groups depend on the quality of their environment, which in turn impacts their ecological dominance and resilience to global change. We then test the model's key predictions using phylogenetic comparative analysis of >6500 bird species. As predicted, we find that cooperative breeders occurring in harsh and fluctuating environments have larger ranges and greater abundances than non‐cooperative breeders, but cooperative breeders occurring in benign and stable environments do not. Using our model, we further show that social species living in harsh and fluctuating environments will be less vulnerable to climate change than non‐social species.

Characterization of a cadmium-resistant functional bacteria (Burkholderia sp. SRB-1) and mechanism analysis at physiochemical and genetic level - Huakang Liu; Huayan Huang; Ke Liang; Kangkai Lin; Yuxian Shangguan; Heng Xu (Environmental Science and Pollution Research, 2023)

Atrazine exposure can dysregulate the immune system and increase the susceptibility against pathogens in honeybees in a dose-dependent manner - Kang Wang; Minqi Cai; Jie Sun; Heng Chen; Zheguang Lin; Zhi Wang; Qingsheng Niu; Ting Ji (Journal of Hazardous Materials, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

An extracellular protease containing a novel C-terminal extension produced by a marine-originated haloarchaeon - Dong Han; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Marine microorganisms have long been acknowledged as a significant reservoir of enzymes required for industrial use. In this study, a novel extracellular protease Hsl HlyB derived from marine-originated haloarchaeon Halostella pelagica DL-M4 T was identified. Hsl HlyB contained polycystic kidney disease (PKD) domain and pre-peptidase C-terminal (PPC) domain at the C-terminus. Truncation and replacement of the C-terminal extension (CTE) of Hsl HlyB demonstrated the importance of the CTE in maintaining the protease activity secreted by haloarchaeon. Hsl HlyB and Hsl HlyBΔCTE were expressed in Escherichia coli BL21(DE3), and purified by high-affinity column refolding and gel filtration chromatography. The molecular masses of Hsl HlyB and Hsl HlyBΔCTE were 42 kDa and 20 kDa, respectively. The optimum catalytic reaction conditions were 50°C, pH 8.5, NaCl 3.5 M and 50°C, pH 7.5, NaCl 3 M, respectively. They showed good stability and hydrolysis capabilities towards a wide range of protein substrates. Hsl HlyBΔCTE showed higher catalytic reaction rate and better thermal stability than the wild type against azocasein and tetrapeptide substrate. The hydrolysates of soybean protein hydrolyzed by Hsl HlyBΔCTE had smaller average molecular masses and shorter average peptide chain lengths than those by Hsl HlyB. These results indicated the diversity of halolysins from marine-originated haloarchaea to harness organic nitrogen in the marine environment and provided promising candidates for application in various industries.

Transcriptome analysis reveals the feeding response and oxidative stress in juvenile Micropterus salmoides fed a low-fish-meal diet with enzyme-hydrolysed intestinal mucosa protein substitution - Heng Yu; Xianping Ge; Lin Zhang; Xiaoru Chen; Mingchun Ren; Hualiang Liang (Aquaculture, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

To close or open the tank input water valve: Secondary water-supply systems with double tanks will induce a higher microbial risk - Dong Hu; Wenfang Lin; Jie Zeng; Heng Zhang; Yating Wei; Xin Yu (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Deep reinforcement learning for class imbalance fault diagnosis of equipment in nuclear power plants - Xianping Zhong; Lin Zhang; Heng Ban (Annals of Nuclear Energy, 2023)

A classification-based approach to mapping particulate organic matter (POM) in inland water using OLCI images - Huaiqing Liu; Wenyu Liu; Jie Lin; Heng Lyu; Yunmei Li; Fangfang Chen; Ying Zhao; Jiafeng Xu; Honglei Guo (Environmental Science and Pollution Research, 2023)

Effects of biodegradation, biotoxicity and microbial community on biostimulation of sulfolane - Shao-Heng Chang; Chi-Wen Lin; Yu-Shen Cheng; Shu-Hui Liu (Chemosphere, 2023)

Elevated temperature affects energy metabolism and behavior of bumblebees - Yun Kuo; Yun-Heng Lu; Yu-Hsien Lin; Yu-Chun Lin; Yueh-Lung Wu (Insect Biochemistry and Molecular Biology, 2023)

Adsorption of heavy metals on biodegradable and conventional microplastics in the Pearl River Estuary, China - Min Shi; Qun Xie; Zhen-Liang Li; Yun-Feng Pan; Zhen Yuan; Lang Lin; Xiang-Rong Xu; Heng-Xiang Li (Environmental Pollution, 2023)

Recycling cinder in efficient methane production from wheat straw via solid-state anaerobic digestion (SS-AD) - Hongyi Lyu; Jing Chen; Mengyi Wang; Huaiwen Zhang; Heng Wu; Tairan Liu; Xuanmin Yang; Xiaohui Guo; Xiaojiao Wang; Ping Ai; Zhenyu Li; Minsong Lin; et al. (Chemical Engineering Journal, 2023)

Natrinema caseinilyticum sp. nov., Natrinema gelatinilyticum sp. nov., Natrinema marinum sp. nov., Natrinema zhouii sp. nov., extremely halophilic archaea isolated from marine environments and a salt mine - Yao Hu; Xue Ma; Xin-Xin Li; Shun Tan; Mu Cheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Halocatena marina sp. nov., a novel filamentous halophilic archaeon isolated from marine tidal flat and emended description of the genus Halocatena - Zhang-Ping Wu; Xi-Wen Zheng; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2023)

Immune and protective effects of subunit vaccines from S-domain or P-domain in capsid protein against nervous necrosis virus in pearl gentian grouper - Tianwen Lin; Jing Xing; Xiaoqian Tang; Xiuzhen Sheng; Heng Chi; Wenbin Zhan (Aquaculture, 2023)

Potential negative effects of illumination on gravity-driven membrane system in treating sulfamethoxazole-containing water - Rui Chen; Han Zhang; Dachao Lin; Jinlong Wang; Yuanqing Guo; Xiaobin Tang; Weijia Gong; Heng Liang (Resources, Conservation and Recycling, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Periodate activation with stable MgMn2O4 spinel for bisphenol A removal: Radical and non-radical pathways - Jiaxin Yu; Wei Qiu; Xinchen Lin; Yishi Wang; Xiaohui Lu; Yongbo Yu; Haiteng Gu; Song Heng; Haochen Zhang; Jun Ma (Chemical Engineering Journal, 2023)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Water infiltration and soil-water characteristics of compacted loess under applied vertical stress - Lin Zhang; Tong-lu Li; Ji-heng Li; Wei Liang; Cun-li Chen (Journal of Mountain Science, 2023)

Microbial response to antimony-arsenic distribution and geochemical factors at arable soil around an antimony mining site - Huayan Huang; Kangkai Lin; Ling Lei; Yongyun Li; Yipeng Li; Ke Liang; Yuxian Shangguan; Heng Xu (Environmental Science and Pollution Research, 2023)

Effect of nanoparticles additives on tribological behaviour of advanced biofuels - Dong Lin Loo; Yew Heng Teoh; Heoy Geok How; Thanh Danh Le; Huu Tho Nguyen; Tazien Rashid; Daphiny Pottmaier; Farooq Sher (Fuel, 2023)

A review on production and implementation of hydrogen as a green fuel in internal combustion engines - Yew Heng Teoh; Heoy Geok How; Thanh Danh Le; Huu Tho Nguyen; Dong Lin Loo; Tazien Rashid; Farooq Sher (Fuel, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Preparation of Co3O4@carbon nanotubes modified ceramic membrane for simultaneous catalytic oxidation and filtration of secondary effluent - Xiaoxiang Cheng; Yongrui Zhang; Qingshui Fan; Lin Wang; Shuai Shi; Xinsheng Luo; Xuewu Zhu; Daoji Wu; Heng Liang (Chemical Engineering Journal, 2023)

Short telomeres impede germ cell specification by upregulating MAPK and TGFβ signaling - Chenglei Tian; Dai Heng; Nannan Zhao; Linlin Liu; Xiaoyan Sheng; Jiyu Chen; Lin Liu (Science China Life Sciences, 2023)

Halorarius litoreus gen. nov., sp. nov., Halorarius halobius sp. nov., Haloglomus halophilum sp. nov., Haloglomus salinum sp. nov., and Natronomonas marina sp. nov., extremely halophilic archaea isolated from tidal flat and marine solar salt - Ya-Ping Sun; Bei-Bei Wang; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Frontiers in Marine Science, 2023)
Five novel halophilic archaeal strains, named BND22 T , ZY10 T , ZY41 T , ZY58 T , and ZY43 T , were isolated from the coastal saline sediment of the intertidal zone located in Qingdao and the natural sea salt produced from Huanghua marine solar saltern, PRChina. These five strains demonstrated the typical morphology and growth characteristics of haloarchaea. The comparison of 16S rRNA gene revealed that strain BDN22 T was associated with Salinirubellus salinus ZS-35-S2 T (95.2% similarity), strain ZY10 T was related to Halosegnis rubeus F17-44 T (95.1% similarity), both strains ZY41 T and ZY58 T were closely related to Haloglomus irregulare F16-60 T (98.1% and 98.2% similarities, respectively), and strain ZY43 T was close to Natronomonas salina YPL13 T (98.0% similarity). In addition to the 16S rRNA gene, the rpoB′ gene is undoubtedly another important molecular marker for the identification of halophilic archaea, and concatenated-conserved-protein phylogeny was widely used in archaeal classification in recent years. Phylogenetic and phylogenomic analyses based on rpoB′ genes and 122 concatenated archaeal protein genes showed that these haloarchaea construct three different clades and gathered together with the current members of Haloarculaceae . Strains BND22 T and ZY10 T formed two distinct clades separated from Salinirubellus salinus ZS-35-S2 T and Halosegnis members, strains ZY41 T and ZY58 T clustered with Haloglomus irregulare F16-60 T , and strain ZY43 T gathered with the current members of Natronomonas. The ANI, DDH, and AAI values of these five strains against phylogenetic neighbours were no more than 91%, 45%, and 92%, respectively, far below the cut-off values for species delineation, supporting their placements in new taxa. Based on the phenotypic, chemotaxonomic, phylogenetic, and phylogenomic properties, these five strains represent five novel taxa of the family Haloarculaceae , Halorarius litoreus gen. nov., sp. nov. (type strain BND22 T = CGMCC 1.18780 T = JCM 34966 T ), Halorarius halobius sp. nov. (type strain ZY10 T = CGMCC 1.17475 T = JCM 34319 T ), Haloglomus halophilum sp. nov. (type strain ZY41 T = CGMCC 1.17030 T = JCM 34161 T ), Haloglomus salinum sp. nov. (type strain ZY58 T = CGMCC 1.17216 T = JCM 34163 T ), and Natronomonas marina sp. nov. (type strain ZY43 T = CGMCC 1.17202 T = JCM 34162 T ). This is the first report of description of a novel haloarchaeon isolated from a marine intertidal zone.

Potential of Miscanthus floridulus associated with endophytic bacterium Bacillus cereus BL4 to remediate cadmium contaminated soil - Xitong Wang; Shihua Luo; Yahui Chen; Renfeng Zhang; Ling Lei; Kangkai Lin; Chengshu Qiu; Heng Xu (Science of The Total Environment, 2023)

Multidimensional analysis of the essential elements in pregnant women's whole blood and characterization of maternal status by elemental pattern - Min Zhan; Wenbin Chen; Zhichao Wang; Xuhui She; Qiaoxuan Zhang; Heng Dong; Jun Yan; Zhuoyang Li; Liqiao Han; Haibiao Lin; Xianzhang Huang; Beibei Zhao (Journal of Trace Elements in Medicine and Biology, 2023)

Melamine foam derived nitrogen and boron co-doped metal-free electrode for enhanced electro-Fenton degradation of metronidazole - Heng Zhao; Xiaolin Ma; Mingjie Lu; Fengting He; Feifei Lin; Yang Zhang; Jinqiang Zhang; Pei Dong; Chaocheng Zhao; Hongqi Sun (Chemical Engineering Journal, 2023)

Regulating the solventized structure to achieve highly reversible zinc plating/stripping for dendrite-free Zn anode by sulfolane additive - Heng Cao; Xiaomin Huang; Yuanxia Li; Yu Liu; Qiaoji Zheng; Yu Huo; Ruyi Zhao; Jingxin Zhao; Dunmin Lin (Chemical Engineering Journal, 2023)

Intimate interaction of TFSI− anions with MoO3−x oxygen vacancies boost ionic conductivity of cathode-supported solid polymer electrolyte - Rohan Paste; Chintam Hanmandlu; Po-Yu Su; Cheng-Hung Hou; Hsin-An Chen; Chun-Wei Pao; Jing-Jong Shyue; Kuei-Hsien Chen; Heng-Liang Wu; Hong-Cheu Lin; Chih Wei Chu (Chemical Engineering Journal, 2023)

Electron transfer-based peroxydisulfate activation by waste herb residue biochar: Adsorption versus surface oxidation - Xuantong Chen; Zhen Guo; Juemiao Liu; Fei Wu; Cheng Cheng; Heng Lin; Wei Ren; Hui Zhang (Chemical Engineering Journal, 2023)

Halorussus vallis sp. nov., Halorussus aquaticus sp. nov., Halorussus gelatinilyticus sp. nov., Halorussus limi sp. nov., Halorussus salilacus sp. nov., Halorussus salinisoli sp. nov.: six extremely halophilic archaea isolated from solar saltern, salt lake and saline soil - Xi-Wen Zheng; Zhang-Ping Wu; Ya-Ping Sun; Bei-Bei Wang; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Halorientalis salina sp. nov., Halorientalis marina sp. nov., Halorientalis litorea sp. nov.: three extremely halophilic archaea isolated from a salt lake and coarse sea salt - Bei-Bei Wang; Ya-Ping Sun; Zhang-Ping Wu; Xi-Wen Zheng; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Associations of metal profiles in blood with thyroiditis: a cross-sectional study - Yaosheng Luo; Huixian Zeng; Yanshi Ye; Genfeng Yu; Cheng Song; Siyang Liu; Xingying Chen; Yuqi Jiang; Hualin Duan; Yue Li; Shengqing He; Zhi Chen; et al. (Environmental Science and Pollution Research, 2022)
Autoimmune thyroiditis (AIT) is increasingly common, and serological markers include thyroid peroxidase antibody (TPOAb) and thyroglobulin antibody (TgAb). To determine if selected metals influence thyroiditis antibody positivity, this cross-sectional study investigated associations between metals and thyroiditis antibody status. Healthy individuals ( n = 1104) completed a questionnaire and underwent checkups of anthropometric parameters, thyroid function status, and levels of seven metals in blood (magnesium, iron, calcium, copper, zinc, manganese, and lead). Associated profiles of glyco- and lipid metabolism were also established. Logistic regression and restricted cubic spline (RCS) regression analysis were applied to adjudge associations between metals and TPOAb and TgAb status. It was found that, after adjusting for likely cofounding factors, participants with antibody positivity had significantly lower serum concentrations of magnesium and iron. When serum magnesium levels were analyzed in quartiles, the odds ratios of quartile 4 were 0.329–fold (95% confidence interval (CI): 0.167–0647) and 0.259-fold (95% CI 0.177–0.574) that of quartile 1 regarding TPOAb and TgAb positivity ( P = 0.004, 0.003). After adjustment, the RCS analysis detected nonlinear associations between iron and TPOAb and TgAb positivity ( P < 0.01, both). In stratified analyses, these associations regarding magnesium and iron remained for women of reproductive age, but not for postmenopausal women and men. We conclude that lower serum levels of magnesium and iron are associated with incremental positivity of thyroiditis antibodies and may be among the most important metals contributing to AIT in women of reproductive age.

Distribution, sources, and ecological risk of organophosphate esters in the urbanized Jiaozhou Bay, East China - Jianing Lin; Lutao Zhang; Mingxing Zhang; Heng Zhang; Changsheng Guo; Song Feng; Jian Xu (Environmental Science and Pollution Research, 2022)

Effect of Zn2+-Cu2+ combined heavy metal on mechanical properties and microstructure of clayey soil - Qiang Ma; Nian-ze Wu; Heng-lin Xiao; Wen-tao Li; Jun-chen Xiang (Journal of Mountain Science, 2022)

Biomechanical Effects of Bone Atrophy, Implant Design, and Vertical or Tilted of Posterior Implant on All-on-Four Concept Implantation: Finite Element Analysis - Heng-Li Huang; Ting-Wei Lin; Hui-Ling Tsai; Yu-Ling Wu; Aaron Yu-Jen Wu (Journal of Medical and Biological Engineering, 2022)

Experimental investigation on debris flow resistance and entrainment characteristics: effects of the erodible bed with discontinuous grading - Pu Li; Jia-ding Wang; Kai-heng Hu; Hai-jun Qiu; Jia-lin Xie (Journal of Mountain Science, 2022)

Microplastic prevalence in marine fish from onshore Beibu Gulf, South China Sea - Jayamini Bimali Koongolla; Lang Lin; Chang-Ping Yang; Yun-Feng Pan; Heng-Xiang Li; Shan Liu; Xiang-Rong Xu (Frontiers in Marine Science, 2022)
In recent years, microplastics have been widely detected in marine fish and may pose potential risks to fish and human health. Even though microplastic pollution is a critical issue, it represents as yet non-quantified threat for some context in the marine environment. In this study, 271 individuals comprising 32 species of marine fish collected from Beibu Gulf were examined for microplastic prevalence, with an aim to provide data on the abundance, physical classification, and chemical characterization of microplastics in the great bay along South China Sea. The results showed that the occurrence rate of microplastics was 93.7%, and the average abundance of microplastics was 1.02 ± 0.18 items per individual (ranging from 0.03 to 4.00 items per individual). Microplastic accumulation was observed with a great variation in different species, body sizes, living habitats, and feeding habits of marine fishes. The dominant polymers identified by μ-FTIR were polyethylene terephthalate and polypropylene. Fibers, smaller sizes (<1 mm), and transparent color were the major characteristics of the detected microplastics, which might be important factors affecting the bioaccumulation. The present study revealed that microplastics in marine fish is a widespread issue in onshore Beibu Gulf.

Historical trend of probable maximum precipitation in Utah and associated weather types - Hongping Gu; S.‐Y. Simon Wang; Yen‐Heng Lin; Jonathan Meyer; Robert Gillies; Everett Taylor; Binod Pokharel (International Journal of Climatology, 2022)
This study assesses the impact global climate change has had on the theoretical upper limit of precipitation for Utah's watersheds by examining historical trends in probable maximum precipitation (PMP), a metric widely used for dam construction and management. Trends in the factors of PMP driven by both frontal and monsoonal storm scenarios were studied using two networks of surface weather stations and modern gridded datasets spanning 1981–2018. It was found that the historical trend in both 3‐hr and 24‐hr PMP estimations exhibited a statistically significant increasing trend, despite that the magnitude of the trend was sensitive to which dataset was examined and the data's spatial resolution. Over the 24‐hr time scale, an interesting deviation in PMP trends was found where frontal storm events demonstrated increasing PMP trends compared to decreasing PMP trends for monsoonal storm events. However, both storm types demonstrated increasing trends over shorter 3‐hr durations, suggesting a universal increase in convective storm intensity. PMP estimates also demonstrated a dependency on the type and resolution of meteorological data used, where higher‐resolution data generally produced greater PMP values and weaker trends. A discussion on the potential causes of these dependencies is provided. This study implies the need to take the historical PMP trend into account for future PMP estimates, especially when coarse‐resolution data are used for conventional PMP studies.

Natural Feed Supplements Improve Growth, Non-Specific Immune Responses and Resistance against Vibrio alginolyticus in Lates calcarifer - Zhen-Hao Liao; Huai-Ting Huang; Yu-Ru Lin; Bo-Ying Chen; Yi-Fan Lee; Yuan-Heng Lin; Chieh-Yuan Chuang; Fan-Hua Nan (Journal of Marine Science and Engineering, 2022)
This study aimed to investigate the effects of dietary natural feed supplement on the growth performance, non-specific responses, and disease resistance in Lates calcarifer. Three commercial products (A, B, and C) containing a basal probiotic mixture were tested. Product A contained a basal mixture of Paenibacillus sp., Bacillus subtilis, Bacillus amyloliquefaciens, and Lactobacillus rhamnosus (107 cfu/g for each probiotic); product B contained additional Lactobacillus plantarum (1010 cfu/g); and product C contained additional soybean peptides (500 g/kg) and garlic powder (1 g/kg). Each product was supplemented into subject diets at dosages of 1 or 2 g/kg (designated as the A1, A2, B1, B2, C1, and C2 groups, respectively). Following an eight-week trial, growth parameters (specific growth rate and feed conversion ratio), non-specific immune responses (O2− production, phagocytic rate, and phagocytic index), and the results of a challenge test against Vibrio alginolyticus were evaluated. The results show that all probiotic supplement groups exhibited an improvement in growth performance compared to the control group (non-probiotic diet). In terms of non-specific immunity parameters, a significant improvement in O2− production was found in the C2 group, whereas significant improvements in phagocytic activity were found in all the B and C groups. The C2 group displayed optimal O2− production, phagocytic rate, and phagocytic index results. For the challenge test, the C groups showed higher Vibrio resistance than the other experimental groups and the control group. These results suggest that product C, given at dosages of 2 g/kg, may serve as a growth-promoting and immunostimulatory additive for the cultivation of Asian seabass.

Nanosecond pulsed electric fields prime mesenchymal stem cells to peptide ghrelin and enhance chondrogenesis and osteochondral defect repair in vivo - Kejia Li; Litong Fan; Jianjing Lin; Boon Chin Heng; Zhantao Deng; Qiujian Zheng; Jue Zhang; Yangzi Jiang; Zigang Ge (Science China Life Sciences, 2022)

Interleukin-13 Affects the Recovery Processes in a Mouse Model of Hemorrhagic Stroke with Bilateral Tibial Fracture - Ya’nan Yan; Cheng Gao; Guang Chen; Xueshi Chen; Yanglin Wu; Heng Xu; Zhiqi Cheng; Chengliang Luo; Mingyang Zhang; Tao Wang; Jun Lin; Xiping Chen; et al. (Molecular Neurobiology, 2022)

Haloprofundus salilacus sp. nov., Haloprofundus halobius sp. nov. and Haloprofundus salinisoli sp. nov.: three extremely halophilic archaea isolated from salt lake and saline soil - Si-Ya Li; Yu-Jie Xin; Chen-Xi Bao; Jing Hou; Heng-Lin Cui (Extremophiles, 2022)

Evaluation of using comparative intradermal tuberculin test to diagnose bovine tuberculosis in dairy cattle in Taiwan - Heng-Ching Lin; Chishih Chu; Yaochi Su; Jyh-Mirn Lai (Tropical Animal Health and Production, 2022)

piRNAs Interact with Cold-Shock Domain-Containing RNA Binding Proteins and Regulate Neuronal Gene Expression During Differentiation - Charannya Sozheesvari Subhramanyam; Qiong Cao; Cheng Wang; Zealyn Shi-Lin Heng; Zhihong Zhou; Qidong Hu (Molecular Neurobiology, 2022)

Effect of initial deviatoric stress on anisotropy of marine clay during principal stress rotation - Heng Zhuang; Xiuqing Hu; Lin Guo; Li Mingfeng; Wang Chaoliang; Hongke Du; Jingqiang Jin (Marine Georesources & Geotechnology, 2022)

The effects of immersive garden experience on the health care to elderly residents with mild-to-moderate cognitive impairment living in nursing homes after the COVID-19 pandemic - Chung-Heng Hsieh; Cheng-Min Chen; Ju-Yuan Yang; Yen-Ju Lin; Man-Li Liao; Ke-Hsin Chueh (Landscape and Ecological Engineering, 2022)

Chemical constituents from the barks of Melia azedarach and their PTP1B inhibitory activity - Sheng-Nan Zhang; Lin Huang; Rui-Jing Ma; Mei-Feng Yang; Ben-Fu Wei; Hong-Zhi Song; Heng-Shan Wang; Qin-Gang Tan (Natural Product Research, 2021)

The effects of initial deviatoric stress on anisotropy of marine clay and strain components - Heng Zhuang; Mingfeng Li; Chaoliang Wang; Lin Guo; Dikang Zhang; Hongke Du; Yunguo Du (Marine Georesources & Geotechnology, 2021)

Characteristics of expanded polystyrene microplastics on island beaches in the Pearl River Estuary: abundance, size, surface texture and their metals-carrying capacity - Qun Xie; Heng-Xiang Li; Lang Lin; Zhen-Liang Li; Jian-sheng Huang; Xiang-Rong Xu (Ecotoxicology, 2021)

Transcription Factor VAX1 Regulates the Regional Specification of the Subpallium Through Repressing Gsx2 - Yan Wen; Zihao Su; Ziwu Wang; Lin Yang; Guoping Liu; Zicong Shang; Yangyang Duan; Heng Du; Zhenmeiyu Li; Yan You; Xiaosu Li; Zhengang Yang; et al. (Molecular Neurobiology, 2021)

Performance Comparison of the Deep Learning and the Human Endoscopist for Bleeding Peptic Ulcer Disease - Hsu-Heng Yen; Ping-Yu Wu; Pei-Yuan Su; Chia-Wei Yang; Yang-Yuan Chen; Mei-Fen Chen; Wen-Chen Lin; Cheng-Lun Tsai; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2021)
Purpose Management of peptic ulcer bleeding is clinically challenging. Accurate characterization of the bleeding during endoscopy is key for endoscopic therapy. This study aimed to assess whether a deep learning model can aid in the classification of bleeding peptic ulcer disease. Methods Endoscopic still images of patients ( n = 1694) with peptic ulcer bleeding for the last 5 years were retrieved and reviewed. Overall, 2289 images were collected for deep learning model training, and 449 images were validated for the performance test. Two expert endoscopists classified the images into different classes based on their appearance. Four deep learning models, including Mobile Net V2, VGG16, Inception V4, and ResNet50, were proposed and pre-trained by ImageNet with the established convolutional neural network algorithm. A comparison of the endoscopists and trained deep learning model was performed to evaluate the model’s performance on a dataset of 449 testing images. Results The results first presented the performance comparisons of four deep learning models. The Mobile Net V2 presented the optimal performance of the proposal models. The Mobile Net V2 was chosen for further comparing the performance with the diagnostic results obtained by one senior and one novice endoscopists. The sensitivity and specificity were acceptable for the prediction of “normal” lesions in both 3-class and 4-class classifications. For the 3-class category, the sensitivity and specificity were 94.83% and 92.36%, respectively. For the 4-class category, the sensitivity and specificity were 95.40% and 92.70%, respectively. The interobserver agreement of the testing dataset of the model was moderate to substantial with the senior endoscopist. The accuracy of the determination of endoscopic therapy required and high-risk endoscopic therapy of the deep learning model was higher than that of the novice endoscopist. Conclusions In this study, the deep learning model performed better than inexperienced endoscopists. Further improvement of the model may aid in clinical decision-making during clinical practice, especially for trainee endoscopist.

Overexpression of uracil permease and nucleoside transporter from Bacillus amyloliquefaciens improves cytidine production in Escherichia coli - Ruoshuang Ma; Haitian Fang; Huiyan Liu; Lin Pan; Hongyan Wang; Heng Zhang (Biotechnology Letters, 2021)

Evolution of delayed water inrush in fault fracture zone considering time effect - Jiwen Bai; Shaolong Duan; Rentai Liu; Lin Xin; Jiawei Tian; Qingsong Zhang; Heng Ma (Arabian Journal of Geosciences, 2021)

Computed Tomography Super-Resolution Using a Generative Adversarial Network in Bronchoscopy: A Clinical Feasibility Study - Heng-sheng Chao; Tsu-Hui Shiao; Chung-Wei Chou; Fang-Chi Lin; Yu-Te Wu; Der-Ming Liou (Journal of Medical and Biological Engineering, 2021)

Analysis of pressure on the roof of a culvert underneath a ditch with compressible material covered by a geosynthetic layer - Qiang Ma; Jun-Jie Zheng; Heng-lin Xiao (European Journal of Environmental and Civil Engineering, 2021)

Cultivation of halophilic archaea (class Halobacteria) from thalassohaline and athalassohaline environments - Heng-Lin Cui; Mike L. Dyall-Smith (Marine Life Science & Technology, 2021)

Decoding Cortical Glial Cell Development - Xiaosu Li; Guoping Liu; Lin Yang; Zhenmeiyu Li; Zhuangzhi Zhang; Zhejun Xu; Yuqun Cai; Heng Du; Zihao Su; Ziwu Wang; Yangyang Duan; Haotian Chen; et al. (Neuroscience Bulletin, 2021)
Mouse cortical radial glial cells (RGCs) are primary neural stem cells that give rise to cortical oligodendrocytes, astrocytes, and olfactory bulb (OB) GABAergic interneurons in late embryogenesis. There are fundamental gaps in understanding how these diverse cell subtypes are generated. Here, by combining single-cell RNA-Seq with intersectional lineage analyses, we show that beginning at around E16.5, neocortical RGCs start to generate ASCL1 + EGFR + apical multipotent intermediate progenitors (MIPCs), which then differentiate into basal MIPCs that express ASCL1, EGFR, OLIG2, and MKI67. These basal MIPCs undergo several rounds of divisions to generate most of the cortical oligodendrocytes and astrocytes and a subpopulation of OB interneurons. Finally, single-cell ATAC-Seq supported our model for the genetic logic underlying the specification and differentiation of cortical glial cells and OB interneurons. Taken together, this work reveals the process of cortical radial glial cell lineage progression and the developmental origins of cortical astrocytes and oligodendrocytes.

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

Post discharge positive re-tests in COVID-19: common but clinically non-significant - Muhammad Syafiq Abdullah; Pui Lin Chong; Rosmonaliza Asli; Riamiza Natalie Momin; Babu Ivan Mani; Dhiya Metussin; Vui Heng Chong (Infectious Diseases, 2020)

Impact of prophylactic/preemptive donor lymphocyte infusion and intensified conditioning for relapsed/refractory leukemia: a real-world study - Yu Wang; Qi-Fa Liu; De-Pei Wu; Jing-Bo Wang; Xi Zhang; Heng-Xiang Wang; Feng Gao; Shun-Qing Wang; Zi-Min Sun; Jian Ouyang; Kai-Lin Xu; Su-Jun Gao; et al. (Science China Life Sciences, 2020)

Technology-side carbon abatement cost curves for China’s power generation sector - Lin-Ju Chen; Zhen-Hai Fang; Fei Xie; Hai-Kuo Dong; Yu-Heng Zhou (Mitigation and Adaptation Strategies for Global Change, 2020)

Hydrogen sulfide alleviates oxidative stress injury and reduces apoptosis induced by MPP+ in Parkinson’s disease cell model - Lin Liu; Jin Wang; Heng Wang (Molecular and Cellular Biochemistry, 2020)

A new 5α,8α-epidioxysterol with immunosuppressive activity from the South China Sea soft coral Sinularia sp. - Min Yang; Lin-Fu Liang; Heng Li; Wei Tang; Yue-Wei Guo (Natural Product Research, 2020)

Factors affecting the removal of bromate and bromide in water by nanofiltration - Dachao Lin; Heng Liang; Guibai Li (Environmental Science and Pollution Research, 2020)

Halorussus halophilus sp. nov., A Novel Halophilic Archaeon Isolated from a Marine Solar Saltern - Yi Ding; Dong Han; Heng-Lin Cui (Current Microbiology, 2020)

Three-directional analytic signal analysis and interpretation of magnetic gradient tensor - Can-wen Guo; Zhe Xing; Lin-fei Wang; Yong Ma; Heng-fei Huan (Applied Geophysics, 2020)

Genome-wide identification of MAPK cascade genes reveals the GhMAP3K14–GhMKK11–GhMPK31 pathway is involved in the drought response in cotton - Lin Chen; Heng Sun; Fengjiao Wang; Dandan Yue; Xiankun Shen; Weinan Sun; Xianlong Zhang; Xiyan Yang (Plant Molecular Biology, 2020)

Characterization of a novel Cu-containing dissimilatory nitrite reductase from the haloarchaeon Halorussus sp. YCN54 - Jing Hou; Xiao-Yan Yang; Qin Xu; Heng-Lin Cui (Extremophiles, 2020)

lncRNA-XIST protects the hypoxia-induced cardiomyocyte injury through regulating the miR-125b-hexokianse 2 axis - Ji-Lin Fan; Ting-Ting Zhu; Zhen-Yu Xue; Wen-Qing Ren; Jing-Qi Guo; Heng-Yi Zhao; Shi-Liang Zhang (In Vitro Cellular & Developmental Biology - Animal, 2020)

A chemically triggered transition from conflict to cooperation in burying beetles - Bo‐Fei Chen; Mark Liu; Dustin R. Rubenstein; Syuan‐Jyun Sun; Jian‐Nan Liu; Yu‐Heng Lin; Sheng‐Feng Shen (Ecology Letters, 2020)
Although interspecific competition has long been recognised as a major driver of trait divergence and adaptive evolution, relatively little effort has focused on how it influences the evolution of intraspecific cooperation. Here we identify the mechanism by which the perceived pressure of interspecific competition influences the transition from intraspecific conflict to cooperation in a facultative cooperatively breeding species, the Asian burying beetle Nicrophorus nepalensis . We not only found that beetles are more cooperative at carcasses when blowfly maggots have begun to digest the tissue, but that this social cooperation appears to be triggered by a single chemical cue – dimethyl disulfide (DMDS) – emitted from carcasses consumed by blowflies, but not from control carcasses lacking blowflies. Our results provide experimental evidence that interspecific competition promotes the transition from intraspecific conflict to cooperation in N. nepalensis via a surprisingly simple social chemical cue that is a reliable indicator of resource competition between species.

A combination of two novel VARS2 variants causes a mitochondrial disorder associated with failure to thrive and pulmonary hypertension - Hui-Lin Chin; Denise Li-Meng Goh; Furene Sijia Wang; Stacey Kiat Hong Tay; Chew Kiat Heng; Claudia Donnini; Enrico Baruffini; Ophry Pines (Journal of Molecular Medicine, 2019)

Climate of the weakly-forced yet high-impact convective storms throughout the Ohio River Valley and Mid-Atlantic United States - Binod Pokharel; S.-Y. Simon Wang; Jonathan Meyer; Robert Gillies; Yen-Heng Lin (Climate Dynamics, 2019)

A novel SGNH family hydrolase Ali5 with thioesterase activity and a GNSL motif but without a classic GDSL motif from Altererythrobacter ishigakiensis - Li-Guo Hong; Shu-Ling Jian; Ying-Yi Huo; Hong Cheng; Xiao-Jian Hu; Jixi Li; Heng-Lin Cui; Xue-Wei Xu (Biotechnology Letters, 2019)

Haloprofundus halophilus sp. nov., isolated from the saline soil of Tarim Basin - Qin Xu; Heng-Lin Cui; Fanwei Meng (Antonie van Leeuwenhoek, 2019)

Intelligent Classifier: a Tool to Impel Drug Technology Transfer from Academia to Industry - Hui-Heng Lin; Defang Ouyang; Yuanjia Hu (Journal of Pharmaceutical Innovation, 2019)

The synthesized transporter K16APoE enabled the therapeutic HAYED peptide to cross the blood-brain barrier and remove excess iron and radicals in the brain, thus easing Alzheimer’s disease - Zhenyou Zou; Qiqiong Shen; Yanxia Pang; Xin Li; Yongfeng Chen; Xinjuan Wang; Xinhua Luo; Zhongmin Wu; Zhaosheng Bao; Juanli Zhang; Jiawei Liang; Lingjia Kong; et al. (Drug Delivery and Translational Research, 2019)

Characterization and adsorption capacity of potassium permanganate used to modify activated carbon filter media for indoor formaldehyde removal - Shih-Cheng Hu; Ying-Chen Chen; Xin-Zhi Lin; Angus Shiue; Po-Hua Huang; Yen-Che Chen; Shu-Mei Chang; Chao-Heng Tseng; Bin Zhou (Environmental Science and Pollution Research, 2018)

A long-term tropical mesoscale convective systems dataset based on a novel objective automatic tracking algorithm - Xiaomeng Huang; Chenqi Hu; Xing Huang; Yang Chu; Yu-heng Tseng; Guang Jun Zhang; Yanluan Lin (Climate Dynamics, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Full genome sequence of the first bluetongue virus serotype 21 (BTV-21) isolated from China: evidence for genetic reassortment between BTV-21 and bluetongue virus serotype 16 (BTV-16) - Shaomin Qin; Heng Yang; Yixuan Zhang; Zhanhong Li; Jun Lin; Lin Gao; Defang Liao; Yingying Cao; Pengfei Ren; Huachun Li; Jianmin Wu (Archives of Virology, 2018)

Insights into the roles of anammox bacteria in post-treatment of anaerobically-treated sewage - Qian Wang; Giin-Yu Amy Tan; Mohammad Azari; Xiaowu Huang; Martin Denecke; Yujie Men; Jin-Young Jung; Satoshi Okabe; Muhammad Ali; Yu-Tzu Huang; Zhuoying Wu; Wai-hung Lo; et al. (Critical Reviews in Environmental Science and Technology, 2018)

In Vitro Antioxidant, Antihemolytic, and Anticancer Activity of the Carotenoids from Halophilic Archaea - Jing Hou; Heng-Lin Cui (Current Microbiology, 2018)

Effect of winds and waves on salt intrusion in the Pearl River estuary - Wenping Gong; Zhongyuan Lin; Yunzhen Chen; Zhaoyun Chen; Heng Zhang (Ocean Science, 2018)
Salt intrusion in the Pearl River estuary (PRE) is a dynamic process that is influenced by a range of factors and to date, few studies have examined the effects of winds and waves on salt intrusion in the PRE. We investigate these effects using the Coupled Ocean-Atmosphere-Wave-Sediment Transport (COAWST) modeling system applied to the PRE. After careful validation, the model is used for a series of diagnostic simulations. It is revealed that the local wind considerably strengthens the salt intrusion by lowering the water level in the eastern part of the estuary and increasing the bottom landward flow. The remote wind increases the water mixing on the continental shelf, elevates the water level on the shelf and in the PRE and pumps saltier shelf water into the estuary by Ekman transport. Enhancement of the salt intrusion is comparable between the remote and local winds. Waves decrease the salt intrusion by increasing the water mixing. Sensitivity analysis shows that the axial down-estuary wind, is most efficient in driving increases in salt intrusion via wind straining effect.

Halobium Salinum sp. nov., Isolated from a Marine Solar Saltern - Yang Li; Yao Zhou; Zhen-Zhen Lü; Heng-Lin Cui (Current Microbiology, 2018)

Halomarina rubra sp. nov., isolated from a marine solar saltern - Yao Zhou; Yang Li; Zhen-Zhen Lü; Heng-Lin Cui (Archives of Microbiology, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Effects of rapid ascent on the heart rate variability of individuals with and without acute mountain sickness - Ming Ling Yih; Fang-Chi Lin; Heng-Sheng Chao; Han-Chen Tsai; Shi-Chuan Chang (European Journal of Applied Physiology, 2017)

Antimicrobial mechanism of the major active essential oil compounds and their structure–activity relationship - Xian Hui; Ge Yan; Fang-Lin Tian; Heng Li; Wen-Yun Gao (Medicinal Chemistry Research, 2017)

Evolution Mechanism and Rainfall Warning Criteria for Maijianwo Slope in Henan Province, China - Yi-heng Pan; Jian-ping Chen; Li-qing Wu; Wei Wang; Fu-lin Tan (Geotechnical and Geological Engineering, 2017)

Halorussus salinus sp. nov., isolated from a marine solar saltern - Jia-Qi Xu; Wen-Mei Xu; Yang Li; Yao Zhou; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Archives of Microbiology, 2016)

Fungal spondylodiscitis in a patient recovered from H7N9 virus infection: a case study and a literature review of the differences between Candida and Aspergillus spondylodiscitis - Lie-dao Yu; Zhi-yun Feng; Xuan-wei Wang; Zhi-heng Ling; Xiang-jin Lin (Journal of Zhejiang University-SCIENCE B, 2016)

Diagnosing the possible dynamics controlling Sahel precipitation in the short-range ensemble community atmospheric model hindcasts - Yu-heng Tseng; Yen-heng Lin; Min-hui Lo; Shu-chih Yang (Climate Dynamics, 2016)

Unilateral hippocampal inactivation or lesion selectively impairs remote contextual fear memory - Heng Zhou; Qixin Zhou; Lin Xu (Psychopharmacology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Behavioural response of the greater horseshoe bat to geographical variation in echolocation calls - Aiqing Lin; Heng Liu; Yang Chang; Guanjun Lu; Jiang Feng (Behavioral Ecology and Sociobiology, 2016)

Clinacanthus nutans Extracts Modulate Epigenetic Link to Cytosolic Phospholipase A2 Expression in SH-SY5Y Cells and Primary Cortical Neurons - Charlene Siew-Hon Tan; Christabel Fung-Yih Ho; Swan-Ser Heng; Jui-Sheng Wu; Benny Kwong-Huat Tan; Yee-Kong Ng; Grace Y. Sun; Teng-Nan Lin; Wei-Yi Ong (NeuroMolecular Medicine, 2016)

An Epigenetic Mechanism of High Gdnf Transcription in Glioma Cells Revealed by Specific Sequence Methylation - Bao-Le Zhang; Jie Liu; Yu Lei; Ye Xiong; Heng Li; Xiaoqian Lin; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2016)

High seroprevalence of toxoplasma gondii and HIV-1 co-infection among drug users in Yunnan province, southwest China - Xin Chen; Mei Ye; Yan-Heng Zhou; Feng-Liang Liu; Lin Duo; Hong Li; Wei Pang; Yong-Tang Zheng (Science China Life Sciences, 2016)

Reliability back analysis of shear strength parameters of landslide with three-dimensional upper bound limit analysis theory - Lian-Heng Zhao; Shi Zuo; Yu-Liang Lin; Liang Li; Yingbin Zhang (Landslides, 2016)

Halomarina salina sp. nov., isolated from a marine solar saltern - Wen-Mei Xu; Jia-Qi Xu; Yao Zhou; Yang Li; Zhen-Zhen Lü; Jing Hou; Lin Zhu; Heng-Lin Cui (Antonie van Leeuwenhoek, 2016)

Complete genome sequence of a Chuzan virus strain isolated for the first time in mainland China - Heng Yang; Lei Xiao; Jinxing Meng; Heli Xiong; Lin Gao; Defang Liao; Huachun Li (Archives of Virology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Degradation of artificial sweetener saccharin in aqueous medium by electrochemically generated hydroxyl radicals - Heng Lin; Jie Wu; Nihal Oturan; Hui Zhang; Mehmet A. Oturan (Environmental Science and Pollution Research, 2016)

Ambient air particulates and particulate-bound mercury Hg(p) concentrations: dry deposition study over a Traffic, Airport, Park (T.A.P.) areas during years of 2011–2012 - Guor-Cheng Fang; Yen-Heng Lin; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2016)

Potential negative effects of groundwater dynamics on dry season convection in the Amazon River basin - Yen-Heng Lin; Min-Hui Lo; Chia Chou (Climate Dynamics, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

Halorubrum rutilum sp. nov. isolated from a marine solar saltern - Shuai Yin; Zhao Wang; Jia-Qi Xu; Wen-Mei Xu; Pan-Pan Yuan; Heng-Lin Cui (Archives of Microbiology, 2015)

Fully automatic and nonparametric quantification of adipose tissue in fat–water separation MR imaging - Defeng Wang; Lin Shi; Winnie C. W. Chu; Miao Hu; Brian Tomlinson; Wen-Hua Huang; Tianfu Wang; Pheng Ann Heng; David K. W. Yeung; Anil T. Ahuja (Medical & Biological Engineering & Computing, 2015)

Upregulation of centromere protein H is associated with progression of renal cell carcinoma - Xun Wu; Youcheng Lin; Liping Shi; Yi Huang; Caiyong Lai; Yongqiang Wang; Meng Zhang; Shupeng Wang; Baoli Heng; Ganshen Yu; Xinghua Du; Lu Fang; et al. (Journal of Molecular Histology, 2015)

Integrated miRNA and mRNA expression profiling of tension force-induced bone formation in periodontal ligament cells - Maolin Chang; Heng Lin; Meng Luo; Jie Wang; Guangli Han (In Vitro Cellular & Developmental Biology - Animal, 2015)

Halorientalis brevis sp. nov., Isolated from an Inland Salt Lake of China - Pan-Pan Yuan; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Current Microbiology, 2015)

Improvement of 1,3-propanediol production in Klebsiella pneumoniae by moderate expression of puuC (encoding an aldehyde dehydrogenase) - Chengqian Zhu; Xiao Jiang; Yongqiang Zhang; Jie Lin; Shuilin Fu; Heng Gong (Biotechnology Letters, 2015)

Haloarchaeobius amylolyticus sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Xin-Juan Sun; Xi Liang; Xiao-Jing Chen; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2015)

Halosimplex litoreum sp. nov., isolated from a marine solar saltern - Pan-Pan Yuan; Jia-Qi Xu; Wen-Mei Xu; Zhao Wang; Shuai Yin; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Physical regulation of stem cells differentiation into teno-lineage: current strategies and future direction - Jia Lin Chen; Wei Zhang; Ze Yu Liu; Boon Chin Heng; Hong Wei Ouyang; Xue Song Dai (Cell and Tissue Research, 2015)

Novel Link of Anti-apoptotic ATF3 with Pro-apoptotic CTMP in the Ischemic Brain - Chien-Yu Huang; Jin-Jer Chen; Jui-Sheng Wu; Hsin-Da Tsai; Heng Lin; Yu-Ting Yan; Chung Y. Hsu; Yuan-Soon Ho; Teng-Nan Lin (Molecular Neurobiology, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Anxiolytic effects of ketamine in animal models of posttraumatic stress disorder - Li-Ming Zhang; Wen-Wen Zhou; Ya-Jun Ji; Ying Li; Nan Zhao; Hong-Xia Chen; Rui Xue; Xin-Guo Mei; You-Zhi Zhang; Heng-Lin Wang; Yun-Feng Li (Psychopharmacology, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Halorussus ruber sp. nov., isolated from an inland salt lake of China - Wei-Dong Xu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Kun Yang (Archives of Microbiology, 2015)

Halorubrum laminariae sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui (Antonie van Leeuwenhoek, 2015)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

Halobacterium rubrum sp. nov., isolated from a marine solar saltern - Dong Han; Heng-Lin Cui (Archives of Microbiology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Halopenitus salinus sp. nov., isolated from the brine of salted brown alga Laminaria - Dong Han; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2014)

Galectin-1 induces vascular permeability through the neuropilin-1/vascular endothelial growth factor receptor-1 complex - Ming-Heng Wu; Nien-Wen Ying; Tse-Ming Hong; Wei-Fan Chiang; Yueh-Te Lin; Yuh-Ling Chen (Angiogenesis, 2014)

Concentrations of particulates in ambient air, gaseous elementary mercury (GEM), and particulate-bound mercury (Hg(p)) at a traffic sampling site: a study of dry deposition in daytime and nighttime - Guor-Cheng Fang; Yen-Heng Lin; Chia-Ying Chang; Yu-Cheng Zheng (Environmental Geochemistry and Health, 2014)

Modulation of angiogenesis by thyroid hormone and hormone analogues: implications for cancer management - Shaker A. Mousa; Hung-Yun Lin; Heng Yuan Tang; Aleck Hercbergs; Mary K. Luidens; Paul J. Davis (Angiogenesis, 2014)

Halorubrum salinum sp. nov., isolated from a marine solar saltern - Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2014)

Haloarchaeobius litoreus sp. nov., isolated from a marine solar saltern - Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2014)

Haloplanus litoreus sp. nov. and Haloplanus ruber sp. nov., from a marine solar saltern and an aquaculture farm, respectively - Dong Han; Heng-Lin Cui (Antonie van Leeuwenhoek, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Erratum to: Salinarubrum litoreum gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from Chinese marine solar salterns - Heng-Lin Cui; Xing-Xing Qiu (Antonie van Leeuwenhoek, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Salinarubrum litoreum gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from Chinese marine solar salterns - Heng-Lin Cui; Xing-Xing Qiu (Antonie van Leeuwenhoek, 2014)

Development of Cre–loxP technology in zebrafish to study the regulation of fish reproduction - Heng-Ju Lin; Shu-Hua Lee; Jen-Leih Wu; Yeh-Fang Duann; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2013)

Haloplanus salinus sp. nov., an extremely halophilic archaeon from a Chinese marine solar saltern - Xing–Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Archives of Microbiology, 2013)

Halorubrum rubrum sp. nov., an extremely halophilic archaeon from a Chinese salt lake - Xing-Xing Qiu; Mei-Lin Zhao; Dong Han; Wen-Jiao Zhang; Heng-Lin Cui (Antonie van Leeuwenhoek, 2013)

Vascular endothelial growth factor (VEGF) gene polymorphisms and risk of head and neck cancer: a meta-analysis involving 2,444 individuals - Wei-Dong Leng; Mei-Ni He; Qi-Lin Chen; Heng Gong; Li Zhang; Xian-Tao Zeng (Molecular Biology Reports, 2013)

Hesperetin protects against cardiac remodelling induced by pressure overload in mice - Wei Deng; Duan Jiang; Yi Fang; Heng Zhou; Zhihong Cheng; Yafen Lin; Rui Zhang; Jieyu Zhang; Peng Pu; Yuan Liu; Zhouyan Bian; Qizhu Tang (Journal of Molecular Histology, 2013)

Functional analyses of a flavonol synthase–like gene from Camellia nitidissima reveal its roles in flavonoid metabolism during floral pigmentation - Xing-Wen Zhou; Zheng-Qi Fan; Yue Chen; Yu-Lin Zhu; Ji-Yuan Li; Heng-Fu Yin (Journal of Biosciences, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

High-Level Expression of Sporamin in Transgenic Chinese Cabbage Enhances Resistance Against Diamondback Moth - Lin Qiu; Tingting Wu; Heng Dong; Linlin Wu; Jiashu Cao; Li Huang (Plant Molecular Biology Reporter, 2013)

MicroRNA-338-3p promotes differentiation of mDPC6T into odontoblast-like cells by targeting Runx2 - Qin Sun; Huan Liu; Heng Lin; Guohua Yuan; Lu Zhang; Zhi Chen (Molecular and Cellular Biochemistry, 2013)

Purification and characterization of alkaline phosphatase from the gut of sea cucumber Stichopus japonicus - Hai-Tao Wu; Dong-Mei Li; Bei-Wei Zhu; Jing-Heng Cheng; Jin-Jian Sun; Feng-Lin Wang; Yang Yang; Yu-Kun Song; Chen-Xu Yu (Fisheries Science, 2013)

Predictors of First-Week Mortality in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shang-Lin Chiang; Heng-Yi Chu; Shin-Tsu Chang; Liang-Cheng Chen (The Cerebellum, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Establishment and characterization of a tamoxifen-mediated reversible immortalized mouse dental papilla cell line - Heng Lin; Huan Liu; Qin Sun; Guohua Yuan; Lu Zhang; Zhi Chen (In Vitro Cellular & Developmental Biology - Animal, 2013)

Halohasta litorea gen. nov. sp. nov., and Halohasta litchfieldiae sp. nov., isolated from the Daliang aquaculture farm, China and from Deep Lake, Antarctica, respectively - Yun-Zhuang Mou; Xing-Xing Qiu; Mei-Lin Zhao; Heng-Lin Cui; Dickson Oh; Mike L. Dyall-Smith (Extremophiles, 2012)

Larval Japanese eel ( Anguilla japonica ) as sub‐surface current bio‐tracers on the East Asia continental shelf - YU‐SAN HAN; HENG ZHANG; YU‐HENG TSENG; MAO‐LIN SHEN (Fisheries Oceanography, 2012)
Larval Japanese eel (leptocephali) are passively transported from their spawning sites of the North Equatorial Current to the Kuroshio and its branch waters for 4–6 months before reaching the East Asian coasts. The larvae mainly stay within water depths between 50–150 m. The dispersal dynamics of larvae thus should reflect the sub‐surface oceanic currents on the East Asia continental shelf. An analysis of Japanese glass eel catch data in East Asian countries during 1985 to 2009, and for Taiwan from 1968 to 2008, indicates that the overall annual catch is generally correlated across countries of East Asia, and between north and west areas of Taiwan. The Kuroshio and its branch waters disperse glass eels throughout East Asian habitats, and the glass eel distribution matches the flow directionality of oceanic currents. Recruitment in western Taiwan occurs with a sequential southwestern to northwestern direction, suggesting that the Taiwan Strait Current penetrates the western coast of Taiwan in the sub‐surface layer in winter. The monthly averaged sub‐surface 50 m circulation pattern in the vicinity of Taiwan and modeled tracer experiments also support the northward winter sub‐surface current in Taiwan Strait. These results suggest that the larval Japanese eel could serve as a valuable bio‐tracer of sub‐surface currents, and the earlier recruitment dynamics of Japanese glass eels in Taiwan could be a good predictor for the subsequent catch in other East Asia areas.

Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Evaluating the prevalence and molecular epidemiology of echovirus 11 isolated from sewage in Shandong Province, China in 2010 - Jing Yang; Ning Cui; Haiyan Wang; Zexin Tao; Yao Liu; Heng Zhang; Hiromu Yoshida; Yanyan Song; Yong Zhang; Lizhi Song; Yan Li; Xiaojuan Lin; et al. (Virus Genes, 2012)

Modeling and assessment of bridge structure for seismic hazard prevention - Jeng-Wen Lin; Cheng-Wu Chen; Shang-Heng Chung (Natural Hazards, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

Salinarchaeum laminariae gen. nov., sp. nov.: a new member of the family Halobacteriaceae isolated from salted brown alga Laminaria - Heng-Lin Cui; Xin Yang; Yun-Zhuang Mou (Extremophiles, 2011)

Simultaneous Effects of Lead and Cadmium on Primary Cultures of Rat Proximal Tubular Cells: Interaction of Apoptosis and Oxidative Stress - Lin Wang; Heng Wang; Jingui Li; Dawei Chen; Zongping Liu (Archives of Environmental Contamination and Toxicology, 2011)

No Association of Angiotensin I Converting Enzyme I/D Polymorphism with Domain-Specific Cognitive Function in Aged Men without Dementia - Mu-En Liu; Shih-Jen Tsai; Ti Lu; Cheng-Jee Hong; Ming-Chao Chen; Shoa-Lin Lin; Heng-Liang Yeh; Yan-Chiou Ku (NeuroMolecular Medicine, 2011)

H2S Protects Hippocampal Neurons from Anoxia–Reoxygenation Through cAMP-Mediated PI3K/Akt/p70S6K Cell-Survival Signaling Pathways - Jian-Lin Shao; Xiao-Hong Wan; Yan Chen; Chun Bi; Hong-Mei Chen; Ying Zhong; Xin-Hua Heng; Jin-Qiao Qian (Journal of Molecular Neuroscience, 2011)

The management and planning of citrus orchards at a regional scale with GIS - Wei Wu; Hong-Bin Liu; Heng-Lin Dai; Wei Li; Peng-Shou Sun (Precision Agriculture, 2011)

Halorussus rarus gen. nov., sp. nov., a new member of the family Halobacteriaceae isolated from a marine solar saltern - Heng-Lin Cui; Xia Gao; Xin Yang; Xue-Wei Xu (Extremophiles, 2010)

Effects of artificial grassland establishment on soil nutrients and carbon properties in a black-soil-type degraded grassland - Gao-Lin Wu; Zhen-Heng Liu; Lei Zhang; Tian-Ming Hu; Ji-Min Chen (Plant and Soil, 2010)

Long-term fencing improved soil properties and soil organic carbon storage in an alpine swamp meadow of western China - Gao-Lin Wu; Zhen-Heng Liu; Lei Zhang; Ji-Min Chen; Tian-Ming Hu (Plant and Soil, 2010)

Identification of Flooding-Response Genes in Eggplant Roots by Suppression Subtractive Hybridization - Kuan-Hung Lin; Chun-Heng Lin; Ming-Tsir Chan; Hsiao-Feng Lo (Plant Molecular Biology Reporter, 2010)

The complete mitochondrial genomes of two species from Sinocyclocheilus (Cypriniformes: Cyprinidae) and a phylogenetic analysis within Cyprininae - Xiaoyun Wu; Lin Wang; Shanyuan Chen; Ruiguang Zan; Heng Xiao; Ya-ping Zhang (Molecular Biology Reports, 2010)

Electroporation is a feasible method to introduce circularized or linearized DNA into B. subtilis chromosome - Ming-Ming Yang; Wei-Wei Zhang; Xiao-Ting Bai; Heng-Xin Li; Pei-Lin Cen (Molecular Biology Reports, 2010)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Expression analysis of shikonin-biosynthetic genes in response to M9 medium and light in Lithospermum erythrorhizon cell cultures - Wen-Ju Zhang; Jing Su; Meng-Yue Tan; Gen-Lin Liu; Yan-Jun Pang; Heng-Guan Shen; Jin-Liang Qi; Yonghua Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Preparation and evaluation of danofloxacin mesylate microspheres and its pharmacokinetics in pigs - Chunmei Wang; Diyun Ai; Cuilan Chen; Heng Lin; Jing Li; Hongchun Shen; Weixue Yi; Yuanhua Qi; Haigang Wu; Jiyue Cao (Veterinary Research Communications, 2009)

Indoor Air Distribution of Nitrogen Dioxide and Ozone in Urban Hospitals - Hong-Wen Chen; Chun-Yu Chuang; Heng-To Lin (Bulletin of Environmental Contamination and Toxicology, 2009)

Effect of fencing and grazing on a Kobresia-dominated meadow in the Qinghai-Tibetan Plateau - Gao-Lin Wu; Guo-Zhen Du; Zhen-Heng Liu; Simon Thirgood (Plant and Soil, 2009)

Effects of Lead and/or Cadmium on the Expression of Metallothionein in the Kidney of Rats - Lin Wang; Dawei Chen; Heng Wang; Zongping Liu (Biological Trace Element Research, 2009)

Oxidative stress and apoptotic changes in primary cultures of rat proximal tubular cells exposed to lead - Lin Wang; Heng Wang; Maozhi Hu; Jin Cao; Dawei Chen; Zongping Liu (Archives of Toxicology, 2009)

Intraspecific polymorphism of 16S rRNA genes in two halophilic archaeal genera, Haloarcula and Halomicrobium - Heng-Lin Cui; Pei-Jin Zhou; Aharon Oren; Shuang-Jiang Liu (Extremophiles, 2009)

Pravastatin attenuates carboplatin-induced cardiotoxicity via inhibition of oxidative stress associated apoptosis - Ching-Feng Cheng; Shu-Hui Juan; Jin-Jer Chen; Ying-Chi Chao; His-Hsien Chen; Wei-Shiung Lian; Chun-Yi Lu; Chung-I Chang; Ted-H Chiu; Heng Lin (Apoptosis, 2008)

Fibrarecisin, a novel triterpenoid from Fibraurea recisa with antitumor activity - Jiao-Long Fu; Chang-Heng Tan; Li-Ping Lin; Ji Huang; Da-Yuan Zhu (Natural Product Research, 2007)

Inhibitory effect of trilinolein on endothelin-1-induced c-fos gene expression in cultured neonatal rat cardiomyocytes - Hung-Yu Yang; Ju-Chi Liu; Yen-Ling Chen; Cheng-Hsien Chen; Heng Lin; Jia-Wei Lin; Wen-Ta Chiu; Jin-Jer Chen; Tzu-Hurng Cheng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2005)

Inhibitory effect of resveratrol on angiotensin II-induced cardiomyocyte hypertrophy - Tzu-Hurng Cheng; Ju-Chi Liu; Heng Lin; Neng-Lang Shih; Yen-Ling Chen; Meng-Ting Huang; Paul Chan; Ching-Feng Cheng; Jin-Jer Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2004)

Strategies for agrobiodiversity conservation and promotion: a case from Yunnan, China - Chun-Lin Long; Heng Li; Zhiqin Ouyang; Xiangyun Yang; Qin Li; Bruce Trangmar (Biodiversity and Conservation, 2003)

Ferredoxin from sweet pepper (Capsicum annuum L.) intensifying harpinpss-mediated hypersensitive response shows an enhanced production of active oxygen species (AOS) - Badri Venkata Dayakar; Hao-Jan Lin; Cheng-Hsien Chen; Mang-Jye Ger; Bor- Heng Lee; Chia-Hwei Pai; David Chow; Hsiang-En Huang; Shaw-Yhi Hwang; Mei-Chu Chung; Teng-Yung Feng (Plant Molecular Biology, 2003)

Expression of Pseudomonas amyloderamosa isoamylase gene in Saccharomyces cerevisiae - Pay-Heng Chen; Long-Liu Lin; Wen-Hwei Hsu (Biotechnology Letters, 1998)